A biobased degradable bacteriostatic gynecological medical panty liner and a preparation method thereof

CN122912167APending Publication Date: 2026-10-16HANGZHOU GUYUANSU BIO-BASED MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611428285.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]综上,现有技术仍无法同时实现生物可降解、pH响应精准释药、高效抑菌、舒适透气的协同统一

Benefits of technology

[0084]1.本护垫设置亲肤层与微溶载药功能层双重抑菌体系,亲肤层通过柠檬酸交联将壳聚糖抑菌组分稳固附着于生物基纤维表面,长效发挥基础抑菌作用;功能层构建pH 4.0~5.5环境响应型复合凝胶网络,可根据私密部位弱酸环境实现活性成分平稳缓释,搭配壳聚糖衍生物与多种植物提取物复配体系,用于妇科浅表黏膜、术后轻微创面的清洁与长效抑菌护理,兼具抑味、止痒及肌肤舒缓修护功效;亲肤层综合抑菌率>98%,功能层pH= 4.5模拟环境2h释药率为32.2%~38.5%、8h释药率为86.8%~93.6%,吸收层吸收量为18.2~22.3g,回渗量0.09~0.14g,防漏底层透气率 342~395mm/s ;适用于医用临床场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912167A_ABST
    Figure CN122912167A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of medical nursing materials, and particularly relates to a biobased degradable, pH-responsive precise drug release and bacteriostatic gynecological medical nursing pad and a preparation method thereof. The biobased degradable bacteriostatic gynecological medical nursing pad comprises a skin-friendly layer, a slightly soluble drug-loaded functional layer, an absorption layer and a leakage-proof bottom layer which are sequentially stacked from top to bottom. The skin-friendly layer takes a biobased fiber as a base and loads a water-soluble chitosan bacteriostatic component. The slightly soluble drug-loaded functional layer contains support fibers, a bacteriostatic component, a polysaccharide matrix, a gel matrix and a crosslinking agent, and the bacteriostatic component comprises a chitosan bacteriostatic agent and a plant soothing bacteriostatic component. The absorption layer is prepared by forming a net, heat bonding and embossing from plant fibers, paper pulp and a biobased superabsorbent resin. The leakage-proof bottom layer is prepared by film forming and stretching to form pores using a biobased degradable resin. The medical nursing pad can inhibit bacteria and be breathable, and can be completely degraded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical care materials technology, specifically relating to a bio-based, biodegradable, pH-responsive, precisely drug-releasing, antibacterial gynecological sanitary pad and its preparation method. It is suitable for antibacterial care of superficial gynecological mucosa and minor wounds. Background Technology

[0002] Most commercially available gynecological pads are daily necessities, primarily used for absorbing secretions during menstruation and lacking medical wound care functions. Existing medical gynecological care products are mostly made of non-degradable petroleum-based polymers such as polyethylene and polypropylene, which are difficult to degrade naturally after use, and large-scale disposal can cause serious white pollution. Furthermore, the antibacterial components in existing medical pads have poor stability and are easily lost during use, making it difficult to provide sustained protection for superficial gynecological mucosal wounds.

[0003] Currently, some technologies have attempted to improve the overall performance of sanitary pads through biodegradable materials and functional modifications. For example, patent document CN105616075A discloses a sanitary product structure with a micro-dissolving function. Although it has a certain functional design and process basis, the pH response range for the release of its antibacterial components is 5.0 to 5.5, which does not match the actual physiological pH environment (4.0 to 4.5) of the female private parts. This can easily lead to defects such as insufficient release of functional components and difficulty in fully exerting the antibacterial effect.

[0004] Patent document CN118383945A discloses a functional sanitary pad structure, but does not disclose key process details in industrial production, such as uniform distribution of functional units, selection of compatible adhesives, and stability of composite molding. Furthermore, it does not provide clear verification data on antibacterial performance and biosafety, which poses technical risks such as high difficulty in industrialization and unstable product performance.

[0005] In summary, existing technologies still cannot simultaneously achieve the synergistic effect of biodegradability, pH-responsive precise drug release, highly effective antibacterial properties, and comfortable breathability. Therefore, this invention aims to provide a bio-based biodegradable antibacterial gynecological medical pad and its preparation method. Through a four-layer composite structure design and the construction of a precise drug release system, it overcomes the shortcomings of traditional products and existing technologies, and has significant application value. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a bio-based, biodegradable, antibacterial gynecological sanitary pad. This pad features precise pH-responsive drug release, highly effective antibacterial properties, breathability, and leak prevention, achieving safety, comfort, environmental friendliness, biodegradability, and precise controllable function. The specific solution of this invention is as follows:

[0007] A bio-based biodegradable antibacterial gynecological medical pad is composed of a skin-friendly layer, a pH-responsive micro-soluble drug-carrying functional layer, an absorbent layer, and a leak-proof bottom layer stacked from top to bottom, and then formed by ultrasonic glueless welding and post-processing to obtain the product.

[0008] The skin-friendly layer uses bio-based fibers as the matrix and is loaded with water-soluble chitosan antibacterial components, and is cross-linked with citric acid.

[0009] The pH-responsive microsoluble drug-carrying functional layer contains supporting fibers, a polysaccharide matrix, a gel matrix, antibacterial components, and a cross-linking agent; the antibacterial components include chitosan-based antibacterial agents and plant-based soothing antibacterial components; the polysaccharide matrix and the gel matrix are combined to form a controllable swelling and release system under weakly acidic conditions;

[0010] The absorbent layer is made of plant fibers, pulp and bio-based superabsorbent resin through web formation, thermal bonding and embossing.

[0011] The leak-proof bottom layer is prepared by bidirectional stretching of a bio-based biodegradable resin film to create pores, forming a microporous structure that is breathable but impermeable to liquid.

[0012] In this invention, the skin-friendly layer employs a multi-bio-based fiber composite system, combined with chitosan-citric acid cross-linking antibacterial finishing, resulting in a soft, liquid-wicking surface that achieves contact-based pre-antibacterial action and prevents the loss of active components. The pH-responsive, micro-soluble drug-carrying functional layer constructs a gel-release system adapted to the slightly acidic environment of the female intimate area, enabling controlled release of antibacterial and plant-based soothing active ingredients upon contact with bodily fluids, achieving long-lasting and precise repair and antibacterial effects. The absorbent layer uses bio-based superabsorbent resin combined with plant fibers and biodegradable adhesive fibers, offering rapid water absorption, strong liquid-locking ability, and resistance to backflow under pressure; the entire layer is completely biodegradable. The leak-proof bottom layer uses bio-based biodegradable resin combined with functional additives, bidirectionally stretched to create pores, balancing breathability and liquid barrier leak-proof performance. The four-layer structure is integrally formed using ultrasonic adhesive-free welding, without the addition of chemical adhesives, leaving no irritating residues. The finished product is sterilized by electron beam irradiation, eliminating the need for ethylene oxide and exhibiting excellent biocompatibility. All layers of the pads are made of biodegradable materials. The four-layer structure works together to create an integrated system that combines diversion and pre-bacterial inhibition, targeted slow release, liquid storage and water locking, and breathability and seepage prevention, taking into account both medical care functions and green environmental protection advantages.

[0013] Preferably, the bio-based fibers in the skin-friendly layer are composed of a main fiber, modified fiber, and bonding fiber; based on the total fiber mass: main fiber 55-65 wt%, modified fiber 20-25 wt%, and bonding fiber 15-20 wt%.

[0014] More preferably, the main fiber is selected from one or more of lyocell fiber, bamboo fiber, degreased long-staple cotton fiber, flax fiber, and seaweed fiber; the modified fiber is selected from one or more of alginate viscose fiber, chitosan modified viscose fiber, chitosan lyocell fiber, and aloe vera modified viscose fiber; and the bonding fiber is selected from one or more of PLA staple fiber, PLA / PBAT staple fiber, PLA / PHBV staple fiber, and PHA staple fiber.

[0015] More preferably, the bio-based fiber in the skin-friendly layer is preferably any one of the following compound systems: degreased long-staple cotton fiber + chitosan-modified viscose fiber + PLA / PBAT short fiber, lyocell fiber + degreased long-staple cotton fiber + chitosan-modified viscose fiber + PLA / PBAT short fiber, degreased long-staple cotton fiber + chitosan-modified viscose fiber + aloe vera-modified viscose fiber + PLA / PBAT short fiber, degreased long-staple cotton fiber + chitosan-modified viscose fiber + PLA short fiber + PHA short fiber, degreased long-staple cotton fiber + bamboo fiber + chitosan-modified viscose fiber + alginate viscose fiber + PLA / PBAT short fiber, flax fiber + degreased long-staple cotton fiber + chitosan lyocell fiber + aloe vera-modified viscose fiber + PLA / PHBV short fiber, lyocell fiber + seaweed fiber + chitosan-modified viscose fiber + PLA short fiber + PHA short fiber.

[0016] Preferably, the mass ratio of bio-based fibers to water-soluble chitosan-based antibacterial components in the skin-friendly layer is 100:0.4 to 0.8.

[0017] More preferably, the water-soluble chitosan-based antibacterial component is selected from one or more of carboxymethyl chitosan, hydroxypropyl chitosan, and quaternized chitosan. (Supplementary explanation: The carboxymethyl chitosan, hydroxypropyl chitosan, and quaternized chitosan loaded in the skin-friendly layer are surface antibacterial functional modifiers. They are anchored to the surface of the bio-based fiber through citric acid cross-linking chemical bonds and act only on the skin contact interface of the pad surface. They exert their protective effect by relying on the film barrier and surface contact antibacterial action. These chitosan derivatives are added externally and cross-linked and fixed to the fiber surface. They do not participate in the construction of the film-forming skeleton and only undertake the functions of immediate surface antibacterial, skin-friendly moisturizing, and long-lasting anti-bleeding.)

[0018] More preferably, the skin-friendly layer is cross-linked with a cross-linking finishing solution containing chitosan and citric acid. The amount of water-soluble chitosan added to the cross-linking finishing solution is 1.0-2.0 wt%, and the mass ratio of citric acid to chitosan is 1.0-2.5:1. The cross-linking finishing solution also contains a catalyst and a penetrant. The catalyst is sodium hypophosphite, and the amount added is 10-20 wt% of the mass of citric acid. The penetrant is fatty alcohol polyoxyethylene ether JFC-C, and the amount added is 1-2 g / L based on the volume of deionized water.

[0019] The skin-friendly layer of this invention is a composite of natural main fibers, functional modified fibers, and biodegradable bonding fibers, all of which are biodegradable. The natural main fibers provide a soft, skin-friendly feel and capillary liquid-wicking ability, while the modified fibers optimize biocompatibility and basic protective performance. PLA and PHA-type biodegradable bonding fibers maintain the overall structural stability of the nonwoven fabric. Through a citric acid crosslinking finishing process, water-soluble chitosan derivatives are chemically anchored to the fiber surface. This chitosan derivative acts only as a surface antibacterial modifier and does not participate in the fiber skeleton construction. It can disrupt the microbial cell structure, giving the contact interface a long-lasting, gentle, and natural antibacterial effect, while also possessing the advantages of skin-friendly moisturizing and resistance to liquid erosion.

[0020] Preferably, the pH-responsive microsoluble drug-carrying functional layer comprises, by total mass of supporting fibers, polysaccharide matrix, and gel matrix: supporting fibers 10-15 wt%, polysaccharide matrix 45-50 wt%, and gel matrix 40-45 wt%; and the mass ratio of polysaccharide matrix to gel matrix is ​​1:0.8-1; the crosslinking agent is calcium lactate, and is 2-5 wt% of the total mass of the above three components, with the crosslinking agent added externally; the supporting fibers are selected from one or more of PLA ultrafine short fibers, PHA ultrafine fibers, bamboo pulp ultrafine fibers, and PCL short fibers; the polysaccharide matrix is ​​selected from one or more of quaternized carboxymethyl chitosan, quaternized hydroxypropyl chitosan, and quaternized chitosan; and the gel matrix is ​​selected from one or more of sodium alginate, konjac glucomannan, and pectin. (Supplementary explanation: Quaternized carboxymethyl chitosan, quaternized hydroxypropyl chitosan, and quaternized chitosan in the pH-responsive, slightly soluble drug-carrying functional layer serve as the gel structure framework substrate and are the basic raw materials for the coating solid phase. Together with sodium alginate, konjac glucomannan, and pectin, they construct a pH-responsive three-dimensional gel cross-linking network, determining the pH-responsive characteristics of gel swelling, dissociation, and slight solubility. Their main function is to build a carrier structure for controlled-release drugs. They are the core component for coating formation, and antibacterial properties are only secondary. This part of chitosan participates in calcium ion cross-linking to form a solid gel matrix.)

[0021] More preferably, the mass ratio of chitosan-based antibacterial agent to plant-based soothing antibacterial component in the pH-responsive microsoluble drug-loaded functional layer is 3.0–9.0:1; the total amount of antibacterial component added is 8–15 wt% of the total mass of supporting fiber + polysaccharide matrix + gel matrix; the chitosan-based antibacterial agent is selected from one or more of quaternized carboxymethyl chitosan, quaternized chitosan, and quaternized hydroxypropyl chitosan; the plant-based soothing antibacterial component is selected from one or more of Artemisia argyi extract, Sophora flavescens extract, dipotassium glycyrrhizate, and rosemary extract. (Supplementary explanation: The quaternized modified chitosan in this antibacterial component is a slow-release functional antibacterial active ingredient, which is additionally dispersed and embedded in the network pores formed by the aforementioned polysaccharides and gel matrix. It does not participate in the gel cross-linking to form a backbone, and will be slowly and gradually released with the slow dissolution of the gel surface. It works synergistically with the plant-based soothing extract to achieve long-term antibacterial repair of the private mucosa, which is fundamentally different from the function of chitosan as a structural substrate.)

[0022] More preferably, the antibacterial component is any of the following compound formulations: quaternized carboxymethyl chitosan + Artemisia argyi extract, quaternized chitosan + Sophora flavescens extract, quaternized hydroxypropyl chitosan + rosemary extract, quaternized carboxymethyl chitosan + quaternized hydroxypropyl chitosan + dipotassium glycyrrhizate, quaternized chitosan + Artemisia argyi extract + Sophora flavescens extract, quaternized carboxymethyl chitosan + quaternized chitosan + rosemary extract + dipotassium glycyrrhizate, quaternized carboxymethyl chitosan + quaternized hydroxypropyl chitosan + quaternized chitosan + Sophora flavescens extract.

[0023] This invention's pH-responsive, microsoluble drug-loaded functional layer utilizes a physical three-dimensional support framework constructed from PLA, PHA, bamboo pulp, and PCL ultrafine short fibers to ensure structural stability and resist liquid erosion and disintegration. A polysaccharide matrix (quaternized chitosan derivative) is combined with sodium alginate, konjac glucomannan, and pectin to construct a composite gel network. With the addition of a cross-linking agent, cross-linking nodes are formed, regulating polymer chain movement and imparting pH-responsive characteristics to the system. In a neutral environment (pH≈7.0), the gel forms a dense network through hydrogen and ionic bonds. The chitosan derivative undergoes deprotonation of its amino groups and hydrophobic shrinkage of its molecular chains, resulting in narrow pores and locking in the antibacterial active components with almost no release. In the weakly acidic vaginal environment (pH 4.0–5.5), hydrogen ions from body fluids penetrate the gel, causing the chitosan molecular chains to protonate and expand. The hydrogen bonds and weak ionic cross-links between polysaccharide chains gradually dissociate, and the gel slowly absorbs water and swells. Strong cross-linking nodes prevent overall gel disintegration, with only a trace amount of micro-dissolution occurring on the surface, thus avoiding the sudden release of active ingredients. The gel network pores are dispersed with additional chitosan-based antibacterial agents and plant-based soothing extracts, forming a natural composite antibacterial system. Chitosan derivatives disrupt microbial cell structure, while extracts of Artemisia argyi, Sophora flavescens, and rosemary, along with dipotassium glycyrrhizate, synergistically inhibit bacterial growth, suppress odor, and provide soothing repair. Active components are continuously and uniformly released through the gel surface, targeting the mucous membrane. Supporting fibers continuously constrain the gel, preventing large-area dissolution and prolonging the drug release cycle. This functional layer is structurally stable, pH-targeted and controllable sustained-release, and mild with low irritation. All components exhibit good biocompatibility and are completely biodegradable.

[0024] Preferably, the absorbent layer comprises bio-based superabsorbent resin, plant fiber, composite pulp, and bonding fiber; it is formed by airflow web formation, synchronous spreading, and hot air bonding.

[0025] Preferably, the bio-based superabsorbent resin is a blend of alginate-based superabsorbent resin and cellulose-based superabsorbent resin; more preferably, the mass ratio of the two is 3:7 to 7:3.

[0026] The plant fiber is selected from one or a blend of two of degreased long-staple cotton and bamboo fiber; the preferred mass ratio of degreased long-staple cotton to bamboo fiber is 8:2 to 6:4.

[0027] The composite pulp is selected from one or a combination of softwood pulp and cotton pulp; the preferred mass ratio of softwood pulp to cotton pulp is 9:1 to 7:3.

[0028] The bonding fiber is selected from PLA / PBAT blended fiber and PLA fiber, preferably PLA / PBAT blended fiber;

[0029] The mass percentages of each component in the absorbent layer are as follows: 40-47 wt% bio-based superabsorbent resin, 30-32 wt% plant fiber, 20-23 wt% composite pulp, and 3-5 wt% bonding fiber.

[0030] The absorbent layer of this invention is integrally formed using airflow web formation, simultaneous spreading, and hot air bonding, and is composed of bio-based superabsorbent resin, plant fibers, composite pulp, and bonding fibers. The alginate-based and cellulose-based composite superabsorbent resin possesses excellent liquid absorption, water retention, and anti-backflow capabilities; degreased long-staple cotton and bamboo fibers can quickly channel liquid, improving the layer's fluffiness and breathability; softwood pulp and cotton pulp intertwine and uniformly coat the absorbent resin, preventing resin agglomeration and shedding; PLA / PBAT-type bonding fibers melt upon heating to form bonding nodes, maintaining the core's fluffiness and stability. All components work synergistically to achieve highly efficient liquid conduction and water retention, with a flexible and breathable structure. All components exhibit good biocompatibility, are completely biodegradable, and are compatible with the entire padding system.

[0031] Preferably, the leak-proof bottom layer comprises a base resin, with added toughening agents, slip agents, chain extenders, and pore-forming agents;

[0032] More preferably, the matrix resin is selected from one or more of PLA, PHA, PBS, PCL, and PBAT;

[0033] More preferably, the toughening agent is selected from epoxy vegetable oil toughening agent, the slip agent is selected from erucamide, the chain extender is selected from ADR-4370S epoxy chain extender, and the pore-forming agent is selected from one or more of nano calcium carbonate, talc, and nano silica.

[0034] More preferably, the bio-based toughening agent comprises 0.8–1.5 wt%, the slip agent 0.3–1.0 wt%, the pore-forming agent 10–15 wt%, and the chain extender 0.5–1.2 wt%.

[0035] During preparation, the material is bidirectionally stretched at 70–90℃ to create pores, with a longitudinal stretching ratio of 2.5–4.0 times and a transverse stretching ratio of 2.0–3.5 times, forming a stable microporous structure that is permeable to air but impermeable to liquid.

[0036] In this invention, the leak-proof bottom layer uses biodegradable materials such as PLA, PHA, PBS, PCL, and PBAT as the matrix, and is compounded with bio-based toughening agents, slip agents, and inorganic pore-forming agents; the matrix resin constitutes the main skeleton of the geomembrane, possessing basic film-forming and liquid-barrier capabilities; the bio-based toughening agent improves the resin's brittleness and enhances the membrane's flexibility and bending resistance; the slip agent optimizes processing performance and surface feel, preventing adhesion; the pore-forming agent forms a uniform microporous structure within the membrane through a biaxial stretching process, achieving an effect of air permeability but liquid impermeability.

[0037] Preferably, the four-layer integrated composite is sterilized using ultrasound, and the finished product is sterilized by electron beam irradiation.

[0038] More preferably, the four-layer integrated composite ultrasonic frequency is 20-40 kHz and the power is 800-1500 W; the finished product is sterilized by 8-25 kGy electron beam irradiation.

[0039] In this invention, the skin-friendly fiber forms a capillary channel to evenly guide secretions, citric acid cross-links and fixes chitosan to construct a dual antibacterial barrier, flexible fibers reduce mucosal irritation, and adhesive-free composite ensures smooth cross-layer transport of substances.

[0040] The pH-responsive microsoluble drug-carrying functional layer relies on ultrafine supporting fibers to maintain the stability of the gel skeleton; the polysaccharide-gel complex system enables controlled release of drugs in weakly acidic environments of pH 4.0–5.5, avoiding the sudden release of active substances; the chitosan and plant extract complex system provides bidirectional antibacterial and soothing effects, buffering instantaneous liquid flow.

[0041] The bio-based absorbent layer relies on bio-based water-absorbing resin and plant fibers to achieve rapid liquid absorption and pressurize to prevent backflow, thus preventing liquid accumulation from interfering with the upper gel layer; the fluffy core continuously supports the structure and retains antibacterial components to play a long-term role.

[0042] The breathable and leak-proof bottom layer features a biaxially stretched microporous membrane that achieves liquid resistance and breathability, stabilizes the internal environment of the pad, delays the premature failure of the gel, and buffers external forces while blocking the invasion of external bacteria.

[0043] Four layers of ultrasonic adhesive-free welding composite molding, working synergistically from top to bottom; all layers are made of biodegradable materials, with no chemical adhesive residue, combined with electron beam sterilization, to construct an integrated medical pad system that guides and inhibits bacteria, targets drug release, stores and locks in liquid, and is breathable and leak-proof.

[0044] This invention also provides a bio-based biodegradable antibacterial gynecological sanitary pad and its preparation method, comprising the following steps:

[0045] (1) Preparation of skin-friendly layer: fiber opening, mixing, and impurity removal → multi-compartment cotton blending, cotton opening and cleaning, fine opening, and double cylinder carding into web → three-stage incremental water pressure hydroentangling → antibacterial finishing solution preparation, finishing and impregnation → drying and cross-linking molding;

[0046] (2) Preparation of microsoluble drug-loaded functional layer: ultrafine short fiber dispersion → preparation of polysaccharide gel coating solution → coating on the inner side of the surface layer → low temperature drying and crosslinking to form a pH-responsive microsoluble gel layer;

[0047] (3) Preparation of absorbent layer: plant fiber and pulp are loosened and dispersed → airflow forms a web and bio-based superabsorbent resin is spread simultaneously → negative pressure adsorption → hot air penetration and bonding → micro embossing is formed;

[0048] (4) Preparation of leak-proof bottom layer: granulation of matrix resin and additives → blown film forming → biaxial stretching to form pores → heat setting and winding → self-adhesive coating.

[0049] (5) Ultrasonic adhesive-free welding composite molding and post-processing: The four layers are precisely positioned and aligned → ultrasonic welding composite → edge heat sealing → slicing → folding → packaging → electron beam irradiation sterilization to obtain the finished pad.

[0050] Preferably, in step (1), the loosening process uses a pre-loosening machine with a roller speed of 350-420 r / min and a spacing of 0.8-1.2 mm;

[0051] Preferably, in step (1), the mixing process uses a closed horizontal cotton mixer with a mixing speed of 80-120 r / min and a mixing residence time of 4-6 min;

[0052] Preferably, in step (1), the impurity removal process adopts a combination of airflow and dust cage for impurity removal, with an air pressure of 120-150 Pa and a screen mesh size of 2.0 mm;

[0053] Preferably, in step (1), the multi-compartment cotton blending adopts a 6-8 compartment vertical cotton blending device, the cotton conveying curtain speed at the bottom of the compartment is 8-12 m / min, and the retention and mixing time in the fiber compartment is ≥90s;

[0054] Preferably, in step (1), the opening and cleaning beater speed is 450-520 r / min, the distance between the beater and the dust bar is gradually narrowed from 12 mm at the cotton inlet end to 6 mm at the cotton outlet end, and the dust cage negative pressure is 180-220 Pa.

[0055] Preferably, in step (1), the fine opening uses a comb-type fine opening roller with a rotation speed of 550-620 r / min and a roller spacing of 0.7-1.0 mm;

[0056] Preferably, in step (1), the cylinder rotation speed ratio before and after the double cylinder is combed into a web is 1:2.8 to 1:3.2, the doffer exit speed is 15 to 22 m / min, the surface density of the shaped fiber web is 30 g / m², and the tolerance is ±1.5 g / m².

[0057] Preferably, in step (1), the hydroentanglement reinforcement adopts a 3D perforated mesh curtain, with three stages of increasing water pressure hydroentanglement: the first hydroentanglement is 60 bar for pre-fixation; the second hydroentanglement is 80 bar for enhanced interweaving; and the third hydroentanglement is 100 bar.

[0058] Preferably, in step (1), the antibacterial finishing solution is prepared using room temperature deionized water with a conductivity ≤10μS / cm. The temperature of the preparation vessel is controlled at 40-45℃. Citric acid is added and stirred for 10-15 minutes at a speed of 60-80 r / min. Water-soluble chitosan is added in batches of 2-3 batches, and the stirring speed is increased to 120-150 r / min for 30-40 minutes. The pH of the solution is controlled at 4.5-5.5. The solution is filtered through a 100-mesh filter.

[0059] Preferably, in step (1), the impregnated nonwoven fabric is treated by one dip and one roll, with a roll-off rate of 70-80%;

[0060] Preferably, in step (1), the drying and crosslinking are performed as follows: pre-drying at 70-80℃ for 3-5 min; baking at 150-160℃ for 1-2 min; moisture content <8%;

[0061] Preferably, in step (2), the dispersion temperature of the ultrafine short fibers is 40±2℃, the stirring speed is 400~600 r / min, and the time is 40~60 min;

[0062] Preferably, in step (2), when preparing the polysaccharide gel coating solution, the antibacterial agent is prepared using room temperature deionized water with a conductivity ≤5μS / cm. The temperature of the preparation vessel is controlled at 40-45℃. Supporting fibers are added and stirred. Chitosan-based antibacterial agents are added first and stirred until swollen for 30-40 minutes before adding the gel matrix. The stirring speed is 250-350 r / min for 50-60 minutes. Subsequently, the plant-based soothing and antibacterial components are prepared into a 5wt% mother liquor using deionized water and added. The stirring speed is 200-250 r / min for 25-35 minutes. The calcium lactate crosslinking agent is pre-prepared into a 2wt% calcium chloride aqueous solution. The slurry is allowed to stand for 60-90 minutes to remove bubbles and obtain the coating solution.

[0063] Preferably, in step (2), the coating process is carried out at an ambient temperature of 22-26°C, a relative humidity of 50%-60% for the skin-friendly substrate, and the substrate is flat and smoothed. The substrate tension is controlled at 15-25 N / m. The coating liquid is applied to the inner side of the surface using a slit scraper with a scraper gap of 0.03-0.12 mm. The substrate travel speed is 5-12 m / min. The coating surface density ranges from 5 to 15 g / m², and the dust level in the clean area is ≤100,000.

[0064] Preferably, in step (2), the system is pre-dried at a low temperature of 60-65℃ for 1-2 minutes, and then continuously dried at 60-65℃ for 2-3 minutes, resulting in a system moisture content of <8%.

[0065] Preferably, in step (3), the plant fibers and pulp are loosened and dispersed, the opening machine beater speed is 550-700 r / min, the air velocity in the air duct is 9-11 m / s, the positive pressure in the mixing silo is 0.012-0.018 MPa, the workshop temperature is 22-28℃, and the relative humidity is 55%-65%.

[0066] Preferably, in step (3), the bio-based superabsorbent polymer (SAP) is spread simultaneously with the airflow forming net, and negative pressure airflow is used to form the net. The linear speed of the net forming net is 12-28 m / min, the negative pressure of the net forming bin is -4.0--7.0 kPa, the longitudinal and transverse strength ratio MD:CD = 1.15-1.4:1, the SAP is quantitatively spread with bio-based SAP particles of 80-160 mesh, and the SAP feed rate per unit area is 48-105 g / m².

[0067] Preferably, in step (3), negative pressure adsorption is performed using a forming mesh curtain, with a cavity vacuum degree of -5 to -8 kPa, a pre-pressure roller linear pressure of 0.08 to 0.15 MPa, and a double-smooth roller temperature of 30 to 40°C.

[0068] Preferably, in step (3), hot air penetrates and bonds, and the oven is divided into three sections for temperature control. The temperature of the preheating section is 110-115℃ and the hot air velocity is 2.8-3.5 m / s. The temperature of the main hot melting section is 120-130℃ and the hot air velocity is 3.2-4.0 m / s. The temperature of the slow cooling and shaping section is 105-112℃ and the air velocity is 2.0-2.8 m / s. The pressure difference between the upper and lower penetrating air is 300-500 Pa.

[0069] Preferably, in step (3), the micro-embossing process involves a micro-embossing roller with a protrusion height of 0.12–0.22 mm, a pressure density of 120–180 points / 10 cm², a roller temperature of 55–75°C, and a pressure of 6–12 N / mm. Air cooling is used at 20–25°C with a wind speed of 1.5–2.2 m / s, and the absorbent layer thickness is 1.8–3.8 mm.

[0070] Preferably, in step (4), the matrix resin and additives are blended and granulated, the PLA moisture content is <0.05%, the PLA main material is first premixed for 2 min + pore-forming agent + toughening agent + chain extender + finally the slip agent is added; low speed premixing 150-220 r / min, high speed stirring 800-1100 r / min; twin-screw melt granulation 160-180℃, screw speed: 220-320 r / min, feeding rate: 120-220 kg / h, water cooling 20-30℃, pelleting φ3×2-4mm; hot air drying at 70-80℃ for 6-8h, moisture content <0.1%;

[0071] Preferably, in step (4), the blown film forming process is carried out with the following conditions: the barrel temperature is 165-178°C, the die temperature is 175-185°C, the screw speed is 90-160 r / min, the film bubble traction speed is 15-30 m / min, the air cooling temperature is 22-28°C, the air pressure is 0.02-0.04 MPa, and the film thickness is 18-30 μm.

[0072] Preferably, in step (4), the bidirectional stretching to form holes has a preheating section roller temperature of 70-78°C and a stretching section temperature of 78-90°C; the longitudinal stretching roller speed ratio is 2.5-4.0 times, the transverse temperature is 75-88°C, the transverse stretching ratio is 2.0-3.5 times, and the stretching linear speed is 8-22 m / min.

[0073] Preferably, in step (4), the heat setting and winding are carried out at 80-88°C in the front section and 90-100°C in the back section, with a film dwell time of 8-15 seconds; after setting, cold air at 22-28°C is used, and the winding tension is 12-22 N / m.

[0074] Preferably, in step (4), the anti-slip self-adhesive coating is applied at a temperature of 22-28℃ and an RH of 50%-62%; the linear speed is 8-22 m / min; the slit coating is applied with an adhesive amount of 10-12 g / m²; after coating, a silicone release paper is immediately applied and then the film is rolled up.

[0075] Preferably, in step (5), the four layers are precisely positioned and aligned, and each layer is equipped with an anti-static brush and an anti-static eliminator. The ambient temperature and humidity are 22-28℃ and RH is 50%-62%. The four layers are unwound synchronously at a speed of 8-22 m / min. The unwinding tension is 5-12 N for the surface layer, 7-14 N for the functional layer, 12-22 N for the absorption layer, and 6-13 N for the bottom film. The front and rear double-group photoelectric edge correction is ±0.2 mm.

[0076] Preferably, in step (5), ultrasonic welding is performed, with an ultrasonic frequency of 20-40 kHz and an output power of 800-1500 W. The dot matrix welding bumps are φ1.0-2.0 mm with a dot spacing of 4-8 mm. The strip welding ribs are 1.2-2.5 mm wide with a rib spacing of 6-12 mm. The welding roller pressure is 0.18-0.35 MPa, and the welding roller linear speed is synchronized with the unwinding of the front section at 8-22 m / min.

[0077] Preferably, in step (5), the edge is heat-sealed, the edge is continuously heat-sealed at 110-140°C, the heat-sealing roller pressure is 0.2-0.4 MPa, the sealing width is 3-8 mm, and the roller speed is the same as the ultrasonic speed of 8-22 m / min;

[0078] Preferably, in step (5), the slice is cut at room temperature with a blade gap of 0.02 to 0.05 mm, a cutting accuracy of ±0.5 mm, and a cutting line speed following the previous section of 8 to 22 m / min.

[0079] Preferably, in step (5), the folding is carried out in a Class 10,000 cleanroom, the folding conveyor belt speed is 8-22 m / min, and it is synchronized with the cutting. The folding compaction pressure is 0.05-0.12 MPa.

[0080] Preferably, in step (5), the packaging environment is a Class 10,000 cleanroom with RH 45% to 60%, the packaging is sealed individually, the release paper unwinding tension is 4 to 9 N, and the outer packaging is heat-sealed with a breathable film: sealing temperature 105 to 125℃, sealing pressure 0.15 to 0.3 MPa, sealing width 2 to 4 mm, and linear speed synchronous 8 to 22 m / min;

[0081] Preferably, in step (5), the product is sterilized by electron beam irradiation with a dose of 8-25 kGy and an irradiation environment of 18-28℃. The packaged finished product is stacked in a single layer with a stacking thickness of ≤50 mm and an electron beam energy of 5-10 MeV. After sterilization, the product is left to stand at room temperature and protected from light for 24 hours before being inspected and put into storage.

[0082] Preferably, to ensure the stable weak acid-responsive drug release performance of the gel, the temperature is controlled at ≤65℃ throughout the gel preparation, coating, and curing process to prevent high temperature from damaging the reversible cross-linking structure of the polysaccharide; the four-layer composite process abandons the high-temperature hot pressing process and adopts instantaneous ultrasonic glue-free welding to avoid thermal damage to the pH-responsive cross-linking network of the gel, ensuring the stability of precise and controllable drug release function.

[0083] Compared with the prior art, the present invention has the following beneficial effects:

[0084] 1. This panty liner features a dual antibacterial system consisting of a skin-friendly layer and a micro-soluble drug-loaded functional layer. The skin-friendly layer uses citric acid cross-linking to firmly attach chitosan antibacterial components to the surface of bio-based fibers, providing long-lasting basic antibacterial effects. The functional layer constructs a pH 4.0–5.5 environmentally responsive composite gel network, which can achieve stable and sustained release of active ingredients according to the slightly acidic environment of the intimate area. Combined with a chitosan derivative and a multi-plant extract compound system, it is used for cleaning and long-lasting antibacterial care of superficial gynecological mucosa and minor postoperative wounds, while also having odor-suppressing, anti-itch, and skin-soothing and repairing effects. The skin-friendly layer has a comprehensive antibacterial rate of >98%, the functional layer has a drug release rate of 32.2%–38.5% in a pH=4.5 simulated environment after 2 hours and 86.8%–93.6% after 8 hours, the absorbent layer has an absorption capacity of 18.2–22.3g, a reabsorption capacity of 0.09–0.14g, and the leak-proof bottom layer has a breathability of 342–395mm / s. It is suitable for medical clinical scenarios.

[0085] 2. The structure is rationally designed with four layers working in sequence. The skin-friendly layer is made of a blend of multi-element bio-based fibers, which is soft, breathable, and facilitates smooth liquid drainage. The absorbent layer uses bio-based superabsorbent resin as its core, combined with plant fibers, composite pulp, and biodegradable adhesive fibers. It is formed by a special process, which has strong water absorption and retention capabilities and is not prone to clumping, delamination, or material loss. The leak-proof bottom layer relies on biodegradable resin and functional additives, which are bidirectionally stretched to form a microporous structure, achieving breathability without liquid permeability, effectively preventing leakage and stuffiness. The overall structure is stable and has strong resistance to bending and deformation.

[0086] 3. Green and environmentally friendly: The raw materials for each functional layer of the pad are all biodegradable materials such as PLA, PHA, PCL, cellulose-based materials, and plant fibers. There are no traditional petroleum-based materials that are difficult to degrade. After disposal, it can be completely degraded naturally, which is environmentally friendly and in line with the concept of green development.

[0087] 4. High safety in use: The layers are bonded together using an ultrasonic adhesive-free process, eliminating chemical adhesives and organic solvents, leaving no harmful residues; the finished product is sterilized by electron beam irradiation, with sterilization parameters meeting standards and good biocompatibility, ensuring safety in use throughout the entire process from raw materials and processing to finished product.

[0088] 5. It is easy to industrialize, with reasonable formulation ratios for each layer. The processes such as airflow web formation, hot air bonding, biaxial stretching, and ultrasonic composite are mature and controllable, resulting in good production stability and enabling large-scale mass production. Attached Figure Description

[0089] Figure 1 This is a schematic diagram of the structure of a bio-based biodegradable antibacterial gynecological medical pad according to the present invention.

[0090] Figure 2 This is a schematic diagram illustrating the test data of the beneficial effects of the bio-based biodegradable antibacterial gynecological medical pads prepared according to the present invention.

[0091] Figure 3 The images shown are of the bio-based biodegradable antibacterial gynecological sanitary pads prepared in Example 1. In Example 1, A is a photograph taken from the direction of the skin-friendly layer, and B is a photograph taken from the direction of the silicone release layer. Detailed Implementation

[0092] The present invention will be further described in detail below with reference to the embodiments, but the implementation of the present invention is not limited to the following embodiments.

[0093] All raw materials used in this invention are commercially available.

[0094] Example 1

[0095] (1) Preparation of skin-friendly layer

[0096] S11. Fiber ingredients: Weigh the following according to the mass ratio: 60wt% degreased long-staple cotton as main fiber, 22wt% chitosan-modified viscose fiber as modified fiber, and 18wt% PLA / PBAT short fiber as bonding fiber, with a total input of 10kg.

[0097] S12. Pre-opening, blending, and impurity removal: Raw materials are fed into a pre-opening machine with a roller speed of 380 r / min and a roller spacing of 1.0 mm. The discharged material is transferred to a closed horizontal blending machine with a stirring speed of 100 r / min and a material mixing residence time of 5 min. After mixing, airflow + dust cage composite impurity removal is performed with an air pressure of 135 Pa and a screen aperture of 2.0 mm. Subsequently, the material is fed into a 7-compartment vertical multi-compartment blending machine with a bottom cotton conveying curtain speed of 10 m / min and a fiber bin mixing residence time of 95 s. The blended cotton material is discharged into the opening and cleaning process with a beater speed of 480 r / min, a dust bar spacing that gradually changes from 12 mm at the cotton inlet end to 6 mm at the cotton outlet end, and a dust cage negative pressure of 200 Pa. Then, the material is finely opened by a comb needle type with a roller speed of 580 r / min and a roller spacing of 0.85 mm.

[0098] S13, Double cylinder carding and hydroentangling: The ratio of cylinder speeds before and after the carding machine is 1:3.0, the doffer output speed is 18m / min, and the carding forms a fiber web with a base surface density of 30g / m². The fiber web is conveyed by a 3D perforated mesh curtain and reinforced by three-stage gradient water pressure: the first stage is 60bar pre-fixation, the second stage is 80bar fiber interlacing, and the third stage is 100bar dense reinforcement.

[0099] S14. Preparation of antibacterial crosslinking finishing solution: Use room temperature deionized water with a conductivity ≤10μS / cm. Control the temperature of the mixing vessel at 42℃. Add citric acid, sodium hypophosphite catalyst, and fatty alcohol polyoxyethylene ether JFC-C penetrant in sequence. The amount of penetrant added is 1.5g / L based on the volume of deionized water. Stir at 70r / min for 12min to mix evenly. Add carboxymethyl chitosan in two batches, increase the stirring speed to 135r / min, and continue stirring for 35min. Adjust the pH of the solution to 4.5. Filter through a 100-mesh filter for later use. The mass ratio of fiber to carboxymethyl chitosan is 100:0.5. The mass fraction of water-soluble carboxymethyl chitosan in the finishing solution is 1.5wt%, and the mass ratio of citric acid to carboxymethyl chitosan is 1.6:1. This corresponds to adding 0.8 parts of citric acid per 100 parts of fiber. The mass of sodium hypophosphite added is 15wt% of the total mass of citric acid.

[0100] S15. Impregnation, drying and crosslinking: The spunlace fabric is impregnated and rolled with finishing solution with a rolling rate of 75%; the fabric is first pre-dried at 75℃ for 4 minutes, then baked at 150℃ for 1.5 minutes for crosslinking and curing, and then rapidly cooled by air. After drying, the moisture content of the fabric is <8%, thus obtaining a functional skin-friendly layer.

[0101] (2) Preparation of functional layer

[0102] S21. Raw material weighing: The total solid phase material is 10kg, including 12wt% PLA ultrafine short fiber as supporting fiber, 48wt% quaternized carboxymethyl chitosan as polysaccharide matrix, and 40wt% sodium alginate as gel matrix. The mass ratio of polysaccharide matrix to gel matrix is ​​1:0.83. An additional compound antibacterial agent accounting for 11wt% of the total solid phase mass is added. The antibacterial agent is composed of quaternized carboxymethyl chitosan and Artemisia argyi extract in a mass ratio of 4:1. The crosslinking agent calcium lactate is prepared as a 2wt% aqueous solution for later use. The amount added is 3.5wt% of the total solid phase mass.

[0103] S22. Pre-dispersion of ultrafine short fibers: Deionized water is fed into a reactor at a controlled temperature of 40°C. PLA ultrafine short fibers are added, and the stirring speed is 500 r / min. The mixture is then dispersed at a constant temperature for 50 min until the fibers are uniformly suspended.

[0104] S23. Preparation of polysaccharide gel coating solution: The dispersion system is kept at 42℃. First, quaternized carboxymethyl chitosan (which only forms the coating structure and is not an antibacterial component) is added as the gel skeleton substrate and stirred at 280 r / min for 35 min to swell. Then, sodium alginate is added and stirred at 300 r / min for 55 min to fully swell, forming the basic gel system. Subsequently, the antibacterial component quaternized carboxymethyl chitosan (component 4 / 5 of the antibacterial compound system) is added and mixed well. Then, the pre-prepared 5wt% Artemisia argyi extract stock solution (component 1 / 5 of the antibacterial compound system) is slowly added dropwise, and the stirring speed is reduced to 220 r / min for 30 min. The prepared slurry is allowed to stand at room temperature for 75 min to degas, resulting in a homogeneous coating solution. (Note: The structural substrate chitosan is responsible for cross-linking and film formation, and achieving pH slow-release swelling; the antibacterial chitosan and Artemisia argyi extract are uniformly dispersed in the gel pores, synergistically exerting antibacterial effects.)

[0105] S24. Slit Coating and Low-Temperature Drying: In a Class 100,000 cleanroom environment, the ambient temperature is 24℃, the relative humidity of the skin-friendly substrate is 55%, and the substrate flattening tension is 20N / m; the slit scraper gap is 0.06mm, the skin-friendly layer feeding speed is 8m / min, and the coating is uniformly applied to the inner side of the skin-friendly layer; after coating, a 2wt% calcium lactate aqueous solution is sprayed through atomization to complete cross-linking; then, it is dried in sections, first pre-dried at 60℃ for 2.0min, and then continuously dried at 65℃ until the overall moisture content of the coating is <8%, thus obtaining a preform with a pH-responsive micro-soluble drug-loaded functional layer.

[0106] (3) Preparation of the absorption layer

[0107] S31. Raw material weighing: Total raw material input is 10kg; bio-based superabsorbent polymer is a 3:7 blend of alginate-based superabsorbent polymer and fiber-based superabsorbent polymer, weighing 43wt%; plant fiber is an 8:2 blend of degreased long-staple cotton and bamboo fiber, weighing 32wt%; composite pulp is a 9:1 blend of softwood pulp and cotton pulp, weighing 22wt%; bonding fiber is a PLA / PBAT blend, weighing 3wt%. The workshop ambient temperature is 25℃ and the relative humidity is 60%.

[0108] S32. Opening airflow web forming and SAP synchronous spreading: Degreased long-staple cotton and composite pulp are fed into the opening machine, with a beater speed of 620 r / min, an air duct conveying speed of 10 m / s, and a positive pressure of 0.012 MPa in the mixing bin; negative pressure airflow web forming, with a web curtain linear speed of 20 m / min, a negative pressure of -5.5 kPa in the web forming bin, and a finished fiber web longitudinal and transverse strength ratio of MD:CD = 1.3:1; 120-mesh alginate-based SAP is selected and synchronously and quantitatively spread, with a SAP feed rate of 72 g / m² per unit area; negative pressure adsorption of the forming web curtain, a cavity vacuum degree of -6.5 kPa, a pre-compression roller linear pressure of 0.11 MPa, and a double-roller temperature of 35℃ for room temperature pre-compression.

[0109] S33, Three-stage hot air hot melt bonding: The oven has zoned temperature control, with a preheating section of 112℃ and a hot air velocity of 3.2m / s, a main hot melt section of 125℃ and a wind velocity of 3.6m / s, and a slow cooling and shaping section of 108℃ and a wind velocity of 2.4m / s. The oven has an upper and lower air pressure difference of 400Pa. The bonding between the fibers is achieved by the PLA bonding fibers being heated and melted.

[0110] S34. Micro-embossing and air-cooling: The embossing roller has a bump height of 0.16mm, a pressure density of 125 points / 10cm², a roller temperature of 58℃, and a roller pressure of 9N / mm. After embossing, the roller is cooled by ambient air at 23℃ with a wind speed of 1.8m / s, resulting in a 2.4mm thick sheet-like absorption layer.

[0111] (4) Prepare the leak-proof bottom layer

[0112] S41. Raw material weighing: Total raw material input is 10kg, PLA 60wt%, PBAT 40wt%; pore-forming agent nano-calcium carbonate 10wt%, epoxy vegetable oil toughening agent 1.0wt%, slip agent erucamide 0.5wt%, ADR-4370S epoxy chain extender 0.5wt%. PLA is dried in a hot air oven at 72-76℃ for 5h, controlling the raw material moisture content to <0.05%; PBAT is dried in a hot air oven at 65-69℃ for 4.5h, controlling the moisture content to <0.05%.

[0113] S42. Twin-screw compounding and granulation: The matrix resin is added to a high-speed mixer and premixed at 180 r / min for 2 min; then nano-calcium carbonate, bio-based toughening agent, erucamide, and ADR chain extender are added, and the speed is adjusted to 850 r / min for 3 min to obtain a homogeneous mixture. The twin-screw extrusion gradient temperature control is as follows: Zone 1: 158℃, Zone 2: 166℃, Zone 3: 171℃, Zone 4: 175℃, and die head: 175℃; screw speed: 270 r / min, feed rate: 170 kg / h, extruded strip is water-cooled at 25℃, and pellet size: φ3×3mm; dried with hot air at 60℃ for 4.5 h, with a pellet moisture content of <0.1%.

[0114] S43. Blown film forming: The granulated material is fed into the blown film machine, the barrel temperature is 172°C, the die temperature is 175°C, the screw speed is 120r / min, and the film bubble traction linear speed is 22m / min; air cooling at 25°C and air pressure is 0.03MPa, and the initial film thickness is 28μm.

[0115] S44. Biaxial stretching for pore formation and heat setting: Preheating roller 75℃, stretching zone temperature control 82℃; longitudinal stretching ratio 3.2 times, transverse stretching ratio 2.8 times, stretching linear speed 15m / min; front heat setting 83℃, rear heat setting 88℃, film stays in the setting zone for 12s; 25℃ cold air cooling, winding tension 17N / m, after setting, microporous bottom film thickness 24μm, pore size 0.1~5μm.

[0116] S45, Anti-slip self-adhesive coating: Temperature 22~28℃, RH 50%~62%; Line speed 8~22 m / min; Slot coating, adhesive application amount 10~12 g / m²; Immediately after coating, cover with silicone release paper and then roll up;

[0117] (5) Four-layer composite, finishing and electron beam sterilization

[0118] S51, Four-layer unwinding alignment: Class 10,000 cleanroom, environment 25℃, relative humidity 56%, each layer is equipped with anti-static brush + static eliminator, four layers synchronous unwinding linear speed 15m / min; skin-friendly layer unwinding tension 8N, functional layer 10N, absorption layer 17N, leak-proof bottom film 9N, front and rear photoelectric correction control edge error ≤±0.2mm.

[0119] S52, Ultrasonic Composite Edge Sealing: Ultrasonic equipment parameters: 28kHz, output power 1100W, dot matrix welding bumps φ1.5mm, dot spacing 6mm, welding roller pressure 0.25MPa; continuous edge heat sealing after composite, heat sealing temperature 125℃, roller pressure 0.3MPa, edge sealing width 5mm.

[0120] S53, Sliced ​​and Folded Packaging: Cold cut at room temperature, blade gap 0.03mm, cutting size accuracy ±0.5mm; after cutting, folding is linked, folding compaction pressure 0.08MPa; individually sealed packaging, sealing temperature 115℃, sealing pressure 0.22MPa, sealing width 3mm.

[0121] S54. Electron beam irradiation sterilization: The finished product is stacked in single layers with a thickness of ≤50mm. The irradiation environment is 23℃, the electron beam energy is 7MeV, and the sterilization dose is 12kGy. After sterilization, the product is placed at room temperature in the dark for 24 hours, inspected, and put into storage to obtain the basic gynecological medical pad product of this embodiment.

[0122] Example 2

[0123] (1) Preparation of skin-friendly layer

[0124] S11, Fiber ingredients: Total feed 10kg; Main fibers: Lyocell fiber 45wt%, degreased long-staple cotton fiber 18wt%, modified fiber 22wt% chitosan modified viscose fiber, bonding fiber 15wt% PLA / PBAT short fiber.

[0125] S12, the process is the same as in Example 1.

[0126] S13, the process is the same as in Example 1.

[0127] S14. Preparation of antibacterial crosslinking finishing solution: Deionized water conductivity ≤10μS / cm, temperature controlled at 42℃; fiber: chitosan = 100:0.7; water-soluble chitosan is quaternized chitosan, added at 2wt%; the mass ratio of crosslinking agent citric acid to chitosan is 1.2:1, and the rest of the process is the same as in Example 1.

[0128] S15, The process is the same as in Example 1.

[0129] (2) Preparation of functional layer

[0130] S21. Raw material weighing: Total feed weight 10kg; Supporting fiber PHA ultrafine short fiber 13wt%, polysaccharide matrix quaternized carboxymethyl chitosan 25wt%, quaternized chitosan 20wt%, gel matrix sodium alginate 22wt%, konjac glucomannan 20wt%; Antibacterial component is quaternized chitosan + Sophora flavescens extract (6:1), total antibacterial agent addition 9wt%, the rest of the process is the same as in Example 1.

[0131] S22, Pre-dispersion of ultrafine short fibers: The temperature of the deionized water feeding vessel is controlled at 42°C, and PHA ultrafine short fibers are added. The rest of the process is the same as in Example 1.

[0132] S23. Preparation of polysaccharide gel coating solution: The dispersion system is kept at a temperature of 45°C. First, add quaternized carboxymethyl chitosan and quaternized chitosan, then add sodium alginate and konjac glucomannan, followed by the antibacterial agent component; the rest of the process is the same as in Example 1.

[0133] S24. The process is the same as in Example 1.

[0134] (3) Preparation of the absorption layer

[0135] S31. Raw material weighing: Total raw material input is 10kg; bio-based superabsorbent resin is 45wt% of alginate-based superabsorbent resin and fiber-based superabsorbent resin in a 7:3 ratio; plant fiber is 30wt% of degreased long-staple cotton and bamboo fiber in a 6:4 ratio; composite pulp is 20wt% of softwood pulp and cotton pulp in a 7:3 ratio; bonding fiber is 5wt% of PLA / PBAT blended fiber; workshop ambient temperature is 25℃ and relative humidity is 60%.

[0136] S32, The process is the same as in Example 1.

[0137] S33, The process is the same as in Example 1.

[0138] S34, finished product thickness 3.0mm, other processes are the same as in Example 1.

[0139] (4) Prepare the leak-proof bottom layer

[0140] S41. Raw material weighing: Total raw material input is 10kg, including PLA 20wt%, PHA 20wt%, PBS 20wt%, PCL 20wt%, PBAT 20wt%; pore-forming agent nano-calcium carbonate 15wt%, epoxy vegetable oil toughening agent 0.8wt%, slip agent erucamide 0.6wt%, and ADR-4370S epoxy chain extender 0.6wt%. The remaining processes are the same as in Example 1.

[0141] S42~S45: The process is the same as in Example 1.

[0142] (5) Four-layer composite, finishing and electron beam sterilization

[0143] S51~S54: Unwinding tension, ultrasonic treatment at 28kHz / 1100W, edge sealing, cutting, packaging, and electron beam sterilization. All process parameters are the same as in Example 1.

[0144] Example 3

[0145] (1) Preparation of skin-friendly layer

[0146] S11. Fiber ingredients: Total feed 10kg; Main fiber: 60wt% degreased long-staple cotton fiber, modified fiber: 20wt% chitosan modified viscose fiber, 5wt% aloe vera modified viscose fiber, bonding fiber: 15wt% PLA / PBAT short fiber.

[0147] S12, the process is the same as in Example 1.

[0148] S13, the process is the same as in Example 1.

[0149] S14. Finishing solution: fiber: chitosan = 100:0.8; carboxymethyl chitosan is selected, with an addition amount of 1.0 wt%; the mass ratio of crosslinking agent citric acid to chitosan is 2.5:1; the remaining processes are the same as in Example 1.

[0150] S15, The process is the same as in Example 1.

[0151] (2) Preparation of functional layer

[0152] S21. Raw material weighing: Total feed weight 10kg; Supporting fiber: 11wt% bamboo pulp ultrafine short fiber; Polysaccharide matrix: 26wt% quaternized carboxymethyl chitosan, 20wt% quaternized hydroxypropyl chitosan; Gel matrix: 33wt% sodium alginate, 10wt% pectin; Antibacterial component: quaternized hydroxypropyl chitosan + rosemary extract (8:1); Total antibacterial agent addition: 13wt%; Other processes are the same as in Example 1.

[0153] S22, Pre-dispersion of ultrafine short fibers: Deionized water is fed into a kettle at a controlled temperature of 42°C, and ultrafine short fibers of bamboo pulp are added; the rest of the process is the same as in Example 1.

[0154] S23. Preparation of polysaccharide gel coating solution: The dispersion system is kept at a temperature of 45°C. First, add quaternized carboxymethyl chitosan and quaternized hydroxypropyl chitosan, then add sodium alginate and pectin, followed by the antibacterial agent component; the rest of the process is the same as in Example 1.

[0155] S24. The process is the same as in Example 1.

[0156] (3) Preparation of the absorption layer

[0157] S31. Raw material weighing: Total raw material input is 10kg; Bio-based superabsorbent resin is 44wt% of alginate-based superabsorbent resin and fiber-based superabsorbent resin in a 4:6 ratio; Plant fiber is 31wt% of degreased long-staple cotton; Composite pulp is 21wt% of softwood pulp; Bonding fiber is 4wt% of PLA fiber; Workshop ambient temperature is 25℃ and relative humidity is 60%.

[0158] S32~34: The process is the same as in Example 1.

[0159] (4) Prepare the leak-proof bottom layer

[0160] S41. Raw material weighing: Total raw material input is 10kg, PLA 40wt%, PBS 40wt%, PBAT 20wt%; pore-forming agent nano-calcium carbonate 5wt%, talc powder 5wt%, nano-silica 5wt%, epoxy vegetable oil toughening agent 1.0wt%, slip agent erucamide 0.6wt%, ADR-4370S epoxy chain extender 0.6wt%. The remaining processes are the same as in Example 1.

[0161] S42~S45: The process is the same as in Example 1.

[0162] (5) Four-layer composite, finishing and electron beam sterilization

[0163] S51~S54: Unwinding tension, ultrasonic treatment at 28kHz / 1100W, edge sealing, cutting, packaging, and electron beam sterilization. All process parameters are the same as in Example 1.

[0164] Example 4

[0165] (1) Preparation of skin-friendly layer

[0166] S11, Fiber ingredients: Total feed 10kg; Main fiber: 59wt% degreased long-staple cotton fiber, modified fiber: 21wt% chitosan modified viscose fiber, bonding fiber: 10wt% PLA short fiber, 10wt% PHA short fiber.

[0167] S12, the process is the same as in Example 1.

[0168] S13, the process is the same as in Example 1.

[0169] S14. Finishing solution: fiber: chitosan = 100:0.6; hydroxypropyl chitosan is selected, with an addition amount of 2wt%; the mass ratio of crosslinking agent citric acid to chitosan is 1:1; the remaining processes are the same as in Example 1.

[0170] S15, The process is the same as in Example 1.

[0171] (2) Preparation of functional layer

[0172] S21. Raw material weighing: Total feed weight 10kg; Supporting fiber PLC short fiber 10wt%, polysaccharide matrix quaternized carboxymethyl chitosan 15wt%, quaternized chitosan 15wt%, quaternized hydroxypropyl chitosan 15wt%, gel matrix sodium alginate 15wt%, konjac glucomannan 15wt%, pectin 15wt%; Antibacterial component is quaternized carboxymethyl chitosan + quaternized hydroxypropyl chitosan + dipotassium glycyrrhizate, chitosan antibacterial agent: plant soothing antibacterial component = 8:1, total antibacterial agent addition 14wt%; other processes are the same as in Example 1.

[0173] S22. Add short fibers to the PLC, and the rest of the process is the same as in Example 1.

[0174] S23. First add the polysaccharide matrix, then the gel matrix, and then the antibacterial agent component; the rest of the process is the same as in Example 1.

[0175] S24. The process is the same as in Example 1.

[0176] (3) Preparation of the absorption layer

[0177] S31. Raw material weighing: Total raw material input is 10kg; Bio-based superabsorbent resin is 43wt% of alginate-based superabsorbent resin and fiber-based superabsorbent resin in a 5:5 ratio; Plant fiber is 32wt% of degreased long-staple cotton; Composite pulp is 20wt% of softwood pulp; Bonding fiber is 5wt% of PLA fiber; Workshop ambient temperature is 25℃ and relative humidity is 60%.

[0178] S32~34: The process is the same as in Example 1.

[0179] (4) Prepare the leak-proof bottom layer

[0180] S41~S45: The process is the same as in Example 1.

[0181] (5) Four-layer composite, finishing and electron beam sterilization

[0182] S51~S54: Unwinding tension, ultrasonic treatment at 28kHz / 1100W, edge sealing, cutting, packaging, and electron beam sterilization. All process parameters are the same as in Example 1.

[0183] Example 5

[0184] (1) Preparation of skin-friendly layer

[0185] S11, Fiber ingredients: Total feed 10kg; Main fibers: 53wt% degreased long-staple cotton fiber, 9wt% bamboo fiber; Modified fibers: 16wt% chitosan modified viscose fiber, 7wt% alginate viscose fiber; Bonding fibers: 15wt% PLA / PBAT short fiber.

[0186] S12, the process is the same as in Example 1.

[0187] S13, the process is the same as in Example 1.

[0188] S14. Finishing solution: fiber:chitosan = 100:0.4; carboxymethyl chitosan + quaternized chitosan (1:1), added at 1.0 wt%; the mass ratio of crosslinking agent citric acid to chitosan is 2.5:1, and the rest is the same as in Example 1.

[0189] S15, The process is the same as in Example 1.

[0190] (2) Preparation of functional layer

[0191] S21. Raw material weighing: Total feed weight 10kg; Supporting fibers: PLC short fiber 4wt%, PLA / PBAT short fiber 4wt%, PLA / PHBV short fiber 4wt%, PHA short fiber 3wt%; Polysaccharide matrix: Quaternized carboxymethyl chitosan 10wt%, Quaternized chitosan 10wt%, Quaternized hydroxypropyl chitosan 25wt%; Gel matrix: Sodium alginate 15wt%, Konjac glucomannan 15wt%, Pectin 10wt%; Antibacterial components: Quaternized chitosan + Artemisia argyi extract + Sophora flavescens extract; Chitosan antibacterial agent: Plant soothing antibacterial component = 4:1; Total antibacterial agent addition 9wt%; Other processes are the same as in Example 1.

[0192] S22. Add PLC short fiber and PLA / PBAT short fiber, and the rest of the process is the same as in Example 1.

[0193] S23. First add the polysaccharide matrix, then the gel matrix, and then the antibacterial agent component; the rest of the process is the same as in Example 1.

[0194] S24. The process is the same as in Example 1.

[0195] (3) Preparation of the absorption layer

[0196] S31. Raw material weighing: Total raw material input is 10kg; Bio-based superabsorbent resin is 44wt% of alginate-based superabsorbent resin and fiber-based superabsorbent resin in a 6:4 ratio; Plant fiber is 30wt% of degreased long-staple cotton; Composite pulp is 23wt% of cotton pulp; Bonding fiber is 3wt% of PLA / PBAT blended fiber; Workshop ambient temperature is 25℃ and relative humidity is 60%.

[0197] S32~34: The process is the same as in Example 1.

[0198] (4) Prepare the leak-proof bottom layer

[0199] S41~S45: The process is the same as in Example 1.

[0200] (5) Four-layer composite, finishing and electron beam sterilization

[0201] S51~S54: Unwinding tension, ultrasonic treatment at 28kHz / 1100W, edge sealing, cutting, packaging, and electron beam sterilization. All process parameters are the same as in Example 1.

[0202] Example 6

[0203] (1) Preparation of skin-friendly layer

[0204] S11, Fiber ingredients: Total feed 10kg; Main fibers: 14wt% flax fiber, 46wt% degreased long-staple cotton fiber, 15wt% modified fibers: chitosan lyocell fiber, 8wt% aloe vera modified viscose fiber, and 17wt% bonding fibers: PLA / PHBV short fiber.

[0205] S12, the process is the same as in Example 1.

[0206] S13, the process is the same as in Example 1.

[0207] S14 finishing solution: fiber:chitosan = 100:0.5; quaternized chitosan + hydroxypropyl chitosan (1:1), added at 1.2wt%; the mass ratio of crosslinking agent citric acid to chitosan is 2:1, and the rest is the same as in Example 1.

[0208] S15, The process is the same as in Example 1.

[0209] (2) Preparation of functional layer

[0210] S21. Raw material weighing: Total feed weight 10kg; Supporting fibers PLA / PBAT short fibers 10wt%, PLA / PHBV short fibers 5wt%, polysaccharide matrix quaternized carboxymethyl chitosan 40wt%, gel matrix sodium alginate 45wt%; Antibacterial components quaternized carboxymethyl chitosan + quaternized chitosan + rosemary extract + dipotassium glycyrrhizate, chitosan antibacterial agent: plant soothing antibacterial component = 5:1, total antibacterial agent addition 11wt%, the rest of the process is the same as in Example 1.

[0211] S22, add PLA / PBAT short fibers and PLA / PHBV short fibers, and the rest of the process is the same as in Example 1.

[0212] S23. First add the polysaccharide matrix, then the gel matrix, and then the antibacterial agent component; the rest of the process is the same as in Example 1.

[0213] S24. The process is the same as in Example 1.

[0214] (3) Preparation of the absorption layer

[0215] S31. Raw material weighing: Total raw material input is 10kg; bio-based superabsorbent polymer is a 5:5 blend of alginate-based superabsorbent polymer and fiber-based superabsorbent polymer, weighing 42wt%; plant fiber is a 5:5 blend of degreased long-staple cotton and bamboo fiber, weighing 32wt%; composite pulp is a 6:4 blend of softwood pulp and cotton pulp, weighing 23wt%; bonding fiber is a 3wt% PLA / PBAT blend fiber; workshop ambient temperature is 25℃ and relative humidity is 60%.

[0216] S32~34: The process is the same as in Example 1.

[0217] (4) Prepare the leak-proof bottom layer

[0218] S41~S45: The process is the same as in Example 1.

[0219] (5) Four-layer composite, finishing and electron beam sterilization

[0220] S51~S54: Unwinding tension, ultrasonic treatment at 28kHz / 1100W, edge sealing, cutting, packaging, and electron beam sterilization. All process parameters are the same as in Example 1.

[0221] Example 7

[0222] (1) Preparation of skin-friendly layer

[0223] S11, Fiber ingredients: Total feed 10kg; Main fibers: Lyocell fiber 33wt%, seaweed fiber 28wt%, modified fiber: chitosan modified viscose fiber 24wt%, bonding fiber: PLA short fiber 8wt%, PHA short fiber 7wt%.

[0224] S12, the process is the same as in Example 1.

[0225] S13, the process is the same as in Example 1.

[0226] S14. Finishing solution: Fiber:Chitosan = 100:0.5; Carboxymethyl chitosan + hydroxypropyl chitosan + quaternized chitosan (1:1:1), added at 1.3wt%; The mass ratio of crosslinking agent citric acid to chitosan is 1:1, and the rest is the same as in Example 1.

[0227] S15, The process is the same as in Example 1.

[0228] (3) Preparation of functional layers

[0229] S21. Raw material weighing: Total feed 10kg; Supporting fiber PLA / PBAT short fiber 15wt%, polysaccharide matrix quaternized carboxymethyl chitosan 40wt%, gel matrix sodium alginate 45wt%; Antibacterial components quaternized carboxymethyl chitosan + quaternized hydroxypropyl chitosan + quaternized chitosan + Sophora flavescens extract, chitosan antibacterial agent: plant soothing antibacterial component = 4:1, total antibacterial agent addition 10wt%, the rest of the process is the same as in Example 1.

[0230] S22. Add PLA / PHBV short fibers, and the rest of the process is the same as in Example 1.

[0231] S23. First add the polysaccharide matrix, then the gel matrix, and then the antibacterial agent component; the rest of the process is the same as in Example 1.

[0232] S24. The process is the same as in Example 1.

[0233] (3) Preparation of the absorption layer

[0234] S31. Raw material weighing: Total raw material input is 10kg; bio-based superabsorbent resin is 43wt% of alginate-based superabsorbent resin and fiber-based superabsorbent resin in a 3:7 ratio; plant fiber is 32wt% of degreased long-staple cotton and bamboo fiber in a 5:5 ratio; composite pulp is 22wt% of softwood pulp and cotton pulp in a 7:3 ratio; bonding fiber is 3wt% of PLA / PBAT blended fiber; workshop ambient temperature is 25℃ and relative humidity is 60%.

[0235] S32~34: The process is the same as in Example 1.

[0236] (4) Prepare the leak-proof bottom layer

[0237] S41~S45: The process is the same as in Example 1.

[0238] (5) Four-layer composite, finishing and electron beam sterilization

[0239] S51~S54: Unwinding tension, ultrasonic treatment at 28kHz / 1100W, edge sealing, cutting, packaging, and electron beam sterilization. All process parameters are the same as in Example 1.

[0240] Comparative Example 1

[0241] (1) Preparation of skin-friendly layer

[0242] S11~S15: The formula and all process parameters are the same as in Example 1.

[0243] (2) The functional layer preparation process is eliminated. The difference is that the entire process of functional layer slit coating and drug loading is omitted, and the product changes from a four-layer structure to a three-layer structure.

[0244] (3) Preparation of the absorbent layer and (4) Preparation of the leak-proof bottom layer: The raw materials and processes are all the same as in Example 1.

[0245] (5) Three-layer composite sterilization

[0246] S51: The difference is that the functional layer unwinding is cancelled, and only the skin-friendly layer, absorption layer and bottom film are unwinded simultaneously, while the tension and correction remain unchanged; the difference is that the four-layer unwinding is changed to three-layer unwinding.

[0247] S52~S54: The ultrasonic sealing, cutting, and sterilization parameters are the same as in Example 1.

[0248] Comparative Example 2

[0249] (1) Preparation of the skin-friendly layer: The whole process is the same as in Example 1.

[0250] (2) Preparation of functional layer

[0251] S21: Contains only PLA ultrafine short fibers. The difference lies in the removal of chitosan, sodium alginate, herbal extracts, and calcium chloride, and the use of benzalkonium chloride in the solution. The difference also lies in the elimination of the polysaccharide gel matrix and plant-based antibacterial materials, replacing them with the chemical antibacterial agent benzalkonium chloride.

[0252] S22: The PLA dispersion process remains unchanged to prepare a single-layer nonwoven fabric substrate.

[0253] S23: The gel preparation and cross-linking dropwise steps are eliminated. The difference lies in the absence of sodium alginate swelling and calcium chloride cross-linking to form a gel system.

[0254] S24: Atomized spray antibacterial liquid replaces slot coating, spray amount 50g / m², drying parameters remain unchanged.

[0255] The difference is that the slit quantitative gel coating is replaced with atmospheric pressure single-sided spraying of the drug solution.

[0256] (3) Prepare the absorbent layer, (4) Prepare the leak-proof bottom layer, (5) Four-layer composite sterilization: parameters are the same as in Example 1.

[0257] Comparative Example 3

[0258] (1) Preparation of the skin-friendly layer, (2) Preparation of the functional layer: The entire formulation process is the same as in Example 1.

[0259] (3) Preparation of the absorption layer

[0260] S31: Alginic acid SAP is replaced with PP petroleum-based SAP, while the remaining fiber proportions remain unchanged. The difference lies in replacing bio-based alginic acid SAP with non-degradable polypropylene SAP.

[0261] S32: The difference lies in the elimination of negative pressure airflow web formation and online SAP application. Instead, the fibers are mixed and then laid flat, with SAP manually added later. The difference lies in the elimination of the negative pressure airflow web formation and online quantitative SAP application processes.

[0262] S33: The difference lies in the elimination of the three-stage hot air melting process; acrylic glue is applied by roller and then air-dried at room temperature. The difference is that PLA hot-melt self-adhesive is replaced with water-based adhesive for bonding and shaping.

[0263] S34: Embossing and air cooling are the same as in Example 1.

[0264] (4) Prepare the leak-proof bottom layer; (5) Four-layer composite sterilization: Same as Example 1.

[0265] Comparative Example 4

[0266] (1) Preparation of the skin-friendly layer, (2) Preparation of the functional layer, (3) Preparation of the absorbent layer: all are the same as in Example 1.

[0267] (4) Prepare the leak-proof bottom layer

[0268] S41: The difference lies in the raw material replacement: PE 65wt% + EVA 34wt% + talc 1wt%, eliminating the need for drying. The difference also lies in replacing the fully biodegradable PLA / PBAT substrate with a non-degradable PE / EVA petroleum-based substrate.

[0269] S42~S43: The difference lies in the granulation and blown film temperatures being adapted to petroleum feedstocks; the remaining equipment parameters are the same as in Example 1. The difference lies in the twin-screw extruder and the adjusted extrusion temperature to adapt to polyolefin feedstocks.

[0270] S44: The difference lies in the elimination of biaxial stretching to create micropores; the blown film is directly wound up, resulting in a dense, non-porous bottom film. The difference also lies in the elimination of the biaxial stretching process to create micropores, resulting in a bottom film without permeable micropores.

[0271] (5) Four-layer composite sterilization: Same as Example 1.

[0272] Comparative Example 5

[0273] (1) Preparation of skin-friendly layer

[0274] S11~S13: Fiber ratio, opening, and hydroentangling process are the same as in Example 1.

[0275] S14: The difference lies in the absence of citric acid crosslinking agent in the chitosan aqueous solution. The difference also lies in the fact that the finishing solution eliminates the crosslinking agent citric acid, thus preventing chemical bond crosslinking.

[0276] S15: The difference lies in the elimination of padding and 150℃ baking, with single-sided spray feeding and low-temperature drying at only 75℃. The difference is that the process of padding and high-temperature cross-linking is replaced by single-sided low-pressure spraying, without baking and curing processes, and the chitosan only adheres physically.

[0277] (2) Prepare the functional layer, (3) Prepare the absorbent layer, (4) Prepare the leak-proof bottom layer, (5) Four-layer composite sterilization, same as in Example 1.

[0278] Comparative Example 6

[0279] (1) Preparation of skin-friendly layer

[0280] S11 to S13 remain unchanged; the difference lies in S14, where the amount of chitosan is halved, while the citric acid ratio remains the same; and S15, where the cross-linking process remains unchanged. The difference is that the amount of water-soluble chitosan added to the skin-friendly layer finishing solution is reduced to 50% of the original formula.

[0281] (2) Preparation of functional layer

[0282] The difference in S21 is that the amount of antibacterial compound component added is reduced from 11wt% to 5.5wt%; the remaining coating process is the same as in Example 1. The difference is that the amount of effective antibacterial component added to the functional layer is halved.

[0283] (3) Preparation of the absorption layer

[0284] The difference in S32 is that the amount of alginate SAP applied is reduced from 72g / m² to 36g / m², while the other molding parameters remain unchanged. The difference is that the amount of SAP areal density applied to the absorbent layer is halved.

[0285] (4) Prepare the leak-proof bottom layer, (5) Four-layer composite sterilization: all the same as in Example 1.

[0286] Sample Analysis

[0287] I. Skin-friendly layer test

[0288] 1. The skin-friendly layers obtained in Examples 1-7 were functionally tested, and the results are shown in Table 1:

[0289] Table 1: Results of Functional Testing of the Skin-Friendly Layer

[0290]

[0291] As shown in Table 1, the skin-friendly layers prepared in Examples 1-7 exhibit excellent antibacterial properties. The samples were tested against *Escherichia coli* ATCC 25922 and *Staphylococcus aureus* ATCC 6538 according to GB / T20944.3-2022, achieving inhibition rates of 99.3% and 99.1% respectively, far exceeding the ≥70% limit. *Candida albicans* was tested according to the 2002 edition of the *Disinfection Technical Specifications*, with an inhibition rate of 98.7% based on the 70% inhibition limit, also meeting the requirements. The test results for all three strains indicate strong antibacterial activity, proving that the skin-friendly layer possesses a strong inhibitory ability against common bacteria and fungi, with stable and reliable antibacterial effects, meeting the requirements for use in gynecological medical pads.

[0292] II. Functional Layer Testing

[0293] 1. The functional layers of microsoluble drug-loaded cells obtained in Examples 1-7 were functionally tested, and the results are shown in Table 2:

[0294] Table 2: Functional Detection Results of Microsoluble Drug-Loading Functional Layer

[0295]

[0296] As shown in Table 2, the microsoluble drug-loaded functional layers prepared in Examples 1-7 exhibited excellent performance in all aspects. This material possesses excellent pH response characteristics; at 37℃, the release rate of active ingredients reaches 87.2% within a pH 4.5 weak acid buffer system after 2 hours, demonstrating rapid release of antibacterial active substances. However, after 24 hours in a pH 7.0 neutral environment, the gel swelling rate is only 13.5%, and the matrix structure remains stable, achieving targeted drug release in the environment. Antibacterial tests were conducted on *Escherichia coli* and *Staphylococcus aureus* using the shaking method according to GB / T20944.3-2022, with inhibition rates of 99.4% and 99.2%, respectively. For *Candida albicans*, tests were conducted according to the 2002 edition of the *Disinfection Technical Specifications*, with an inhibition rate of 98.9% based on the 70% inhibition limit. The antibacterial effects of all three strains far exceeded the acceptable threshold, classifying them as highly effective antibacterial agents. In an LPS-induced macrophage inflammation model, the sample showed an inhibition rate of 68.3% against IL-6 and 71.5% against TNF-α, significantly downregulating the secretion level of inflammatory factors and demonstrating outstanding anti-inflammatory and soothing effects. Overall, all indicators of this functional layer met the standards and are suitable for use as a gynecological medical pad.

[0297] III. Absorption Layer Test

[0298] 1. The absorption layers obtained in Examples 1 to 7 were functionally tested, and the results are shown in Table 3:

[0299] Table 3: Results of Functional Testing of Absorbing Layer

[0300]

[0301] As shown in Table 3, the absorbent layers prepared in Examples 1-7 all met the expected design requirements. The products exhibit excellent absorption rates, high absorption, rapid water retention, fast liquid introduction without retention, and excellent backflow prevention performance, with no backflow under pressure, ensuring dry and comfortable use. Simulated usage tests showed that the core did not clump or collapse, maintained a stable and intact structure, demonstrated good overall uniformity, and its areal density met the process specifications. The absorbent layers prepared in this example combine high absorption, strong water retention, no backflow, and structural stability, fully meeting the usage requirements for absorbent cores in gynecological medical pads.

[0302] IV. Leak-proof underlayer test

[0303] 1. The performance of the leak-proof underlayers obtained in Examples 1 to 7 was tested, and the results are shown in Table 4:

[0304] Table 4: Test Results of Leak-proof Substrate Performance

[0305]

[0306] As shown in Table 4, the bio-based biodegradable leak-proof bottom layer prepared in Examples 1 to 7 underwent comprehensive performance testing, and all indicators met the preset requirements, demonstrating excellent overall performance.

[0307] In terms of breathability, the measured average air permeability of the sample was 1120 mm / s, falling within the standard range of 850–1200 mm / s, indicating excellent breathability and no stuffiness during use. Regarding leak-proof performance, the sample withstood an average hydrostatic pressure of 3664 Pa, exceeding the technical specification of ≥3500 Pa, demonstrating excellent liquid resistance and leak-proof capabilities. Mechanical properties meet usage requirements; the film exhibits good flexibility, showing no damage or breakage under stress, and both tensile strength and elongation at break meet standards, making it suitable for product processing and usage scenarios. Biodegradability testing showed that the sample achieved a 92% biodegradability rate after 180 days, exceeding the ≥90% threshold, indicating complete biodegradability and outstanding green and environmentally friendly characteristics.

[0308] In summary, this leak-proof bottom layer balances breathability and leak prevention, has stable mechanical properties, and possesses excellent biodegradability. All indicators meet the usage and design standards for bio-based biodegradable antibacterial gynecological medical pads.

[0309] V. Testing of Finished Gynecological Medical Panty Liners

[0310] 1. The gynecological medical pads obtained in Examples 1-7 were subjected to functional and performance suitability tests. All indicators were tested according to GB / T20944.3-2022, GB / T 16886 series of medical device biological evaluation standards, YY / T 0618-2018, GB / T 8939-2018, and other standards. The results are shown in Table 5.

[0311] Table 5: Test Results of Finished Gynecological Medical Panty Liners

[0312]

[0313] Functional and performance tests were conducted on the gynecological medical pads prepared in Examples 1 to 7. All test items were deemed qualified / compliant, and the products demonstrated excellent overall performance.

[0314] At the pharmacological level, the product exhibits antibacterial rates of 98.8% and 98.5% against Escherichia coli and Staphylococcus aureus, respectively, and an antibacterial rate of 98.2% against Candida albicans (evaluated against the 70% limit), demonstrating potent and broad-spectrum antibacterial capabilities. Under physiological conditions at 37°C, the release rate of active substances is 86.5% after 2 hours in a weakly acidic vaginal environment (pH 4.0–5.5), and the structure remains stable in a neutral environment, achieving targeted and controllable drug release. In in vitro cell anti-inflammatory experiments, the inhibition rates of IL-6 and TNF-α inflammatory factors are 67.8% and 70.2%, respectively, demonstrating clear anti-inflammatory and soothing effects.

[0315] Both blood compatibility and biosafety indicators meet the requirements for medical mucosal contact: in vitro coagulation tests showed that the clotting time of the sample was shortened by 52% compared with the blank group, demonstrating excellent procoagulant and hemostatic effects; designed for hemostasis of superficial wounds, the platelet adhesion rate reached 76%, which can quickly activate the coagulation mechanism; the cytotoxicity level was 1, with only very slight cellular effects, meeting the medical device access standards; the rabbit skin repeated contact irritation score was 0, with no skin irritation reactions such as erythema and edema, indicating high biosafety.

[0316] In terms of physical performance, the core absorbs 22.3g / g according to national standards, 5mL of liquid can be completely absorbed in 3.3s, and the backflow under pressure is only 0.02g, demonstrating excellent absorption, water retention, and dryness. After a simulated wear test under vibration and pressure, the core did not clump or collapse, indicating structural stability. The bottom membrane has an air permeability of 1115mm / s and a hydrostatic pressure resistance of 3658Pa, balancing breathability and leak prevention. The product has a smooth and soft appearance, providing a good skin-friendly experience.

[0317] This series of gynecological medical pads has both antibacterial and anti-inflammatory properties, pH-targeted drug release, and wound hemostasis and coagulation promotion functions. At the same time, it is biosafe and reliable, absorbent and leak-proof, structurally stable, and comfortable to use. It is suitable for antibacterial care of superficial gynecological mucosa and minor wounds.

[0318] 2. Safety tests were conducted on the finished gynecological medical pads from Examples 1 to 7, and the results are shown in Table 6:

[0319] Table 6: Test Results of Finished Gynecological Medical Panty Liners

[0320]

[0321] The gynecological medical pads prepared in Examples 1-7 were subjected to a full range of tests for microbiology, medical biosafety, chemical residues, sterilization, and physicochemical safety. The tests were conducted in accordance with authoritative standards such as GB 15979-2002 Disposable Sanitary Products Standard, GB / T 16886 Medical Device Biological Evaluation Series Standards, and the Chinese Pharmacopoeia. All test items were deemed qualified and met the standards, and the overall safety level of the products met the stringent requirements for gynecological mucosal contact medical products.

[0322] In terms of microbiological hygiene indicators, the total bacterial count was 8 CFU / g and the total fungal count was 3 CFU / g, far below the national standard threshold. Pathogenic microorganisms such as coliforms, Staphylococcus aureus, Pseudomonas aeruginosa, and hemolytic streptococci were not detected. A vaginal mucosal irritation test was conducted according to GB / T 16886.10-2017, and the mucosal irritation score was 0, with no congestion, edema, or erosion, indicating excellent mucosal compatibility.

[0323] The product exhibits excellent performance in sterilization-related tests; it is sterilized using electron beam irradiation, achieving a sterilization index of up to 10. 4 It far exceeds the minimum sterilization requirement of ≥10³; ethylene oxide residue is <0.1μg / g, with almost no EO agent residue; no microbial growth is observed after 14 days of sterile culture, meeting the standards for medical sterile products.

[0324] All chemical safety risk items are compliant: no migratable fluorescent whitening agents were detected; the total amount of heavy metals that can be leached from medical devices is 5.0 ppm, and the free formaldehyde content is 0.02 wt%, both of which are significantly lower than the limit values; according to the national standard for textile moisture content, the finished product moisture content is 7.0 wt%, which is within the reasonable range of 6-9 wt%, and can be stored for a long time without being affected by moisture and the growth of microorganisms.

[0325] Based on comprehensive safety testing data, this series of gynecological medical pads demonstrates excellent performance in terms of microbial cleanliness, mucosal biocompatibility, harmful chemical residues, sterilization safety, and physicochemical stability. They pose no safety risks such as microbial infection, mucosal irritation, or chemical toxin residues, and fully comply with safety standards for intimate gynecological medical care products.

[0326] 3. The degradation performance of the gynecological medical pads obtained in Examples 1-7 was tested, and the results are shown in Table 7:

[0327] Table 7: Test Results of Degradability of Finished Gynecological Medical Panty Liners

[0328]

[0329] As shown in Table 7, the degradation performance test results of the finished products in Examples 1-7 indicate that, under composting conditions, the average biodegradation rate of the sanitary pads reached 91.5% and the average disintegration rate reached 93.2% after 180 days, both exceeding the technical requirement of ≥90%. After 90 days of soil burial, the product gradually crumbled and disintegrated, leaving no intact product residue. The product as a whole can achieve complete biodegradation, will not form plastic waste in the natural environment, and has excellent green and environmentally friendly properties, meeting the design requirements for bio-based biodegradable gynecological medical sanitary pads.

[0330] VI. Performance Comparison Test

[0331] 1. Antibacterial effect test

[0332] The gynecological medical pads prepared in Examples 1-7 and those prepared in Comparative Examples 1-6 were compared in terms of antibacterial effects against Escherichia coli and Staphylococcus aureus according to GB / T 20944.3-2022 Evaluation of Antimicrobial Properties of Textiles Part 3: Shaking Method, and Candida albicans according to the 2002 edition of "Disinfection Technical Specifications". The results are shown in Table 8. Figure 2 As shown.

[0333] Table 8: Antibacterial Efficacy Test Results of Examples 1-7 and Comparative Examples 1-6

[0334]

[0335] Overall, the antibacterial rates of Escherichia coli, Staphylococcus aureus, and Candida albicans in Examples 1-7 of this invention are in the range of 98.5% to 99.8%, demonstrating excellent and stable antibacterial performance; products with different functional orientations only show slight performance fluctuations.

[0336] The antibacterial effects of each comparative example were significantly lower than those of the individual examples: after removing the antibacterial functional layer, canceling the citric acid crosslinking process, and halving the effective antibacterial component, the antibacterial ability of the samples decreased significantly; the antibacterial rate of the samples that were replaced with chemical antibacterial agents, used petroleum-based SAP adhesive bonding systems, and were paired with non-degradable PE / EVA bottom films also decreased to varying degrees. The poor air permeability of the non-degradable bottom film alters the microenvironment of the functional layer and affects the stable and sustained release of active components, indirectly causing a reduction in the antibacterial effect; when the citric acid crosslinking system was not used, the antibacterial components relied solely on physical adhesion and were easily washed away by body fluids, making it difficult to maintain long-term antibacterial ability.

[0337] Test results confirm that the dedicated antibacterial functional layer, citric acid cross-linking and immobilization process, sufficient antibacterial active ingredients, and the bio-based raw material system of this invention are the core conditions for the product to achieve efficient and broad-spectrum antibacterial activity. Compared with traditional non-functional layer structures, chemical antibacterial systems, petroleum-based substrates, and simple physical adhesion processes for antibacterial components, the antibacterial solution of this invention has significant advantages.

[0338] 2. pH-responsive drug release effect test

[0339] The gynecological medical pads prepared in Examples 1-7 and those prepared in Comparative Examples 1-6 were compared using an in vitro drug release test method simulating a weakly acidic human environment (pH=4.5). The release rates of the components were measured at 2 hours and 8 hours, and the results are shown in Table 9. Figure 2 As shown.

[0340] Table 9: Results of pH-responsive drug release tests in Examples 1-7 and Comparative Examples 1-6

[0341]

[0342] In vitro drug release tests were conducted in a simulated weakly acidic vaginal environment at pH 4.5. The results showed that, based on the cross-linked gel sustained-release system, Examples 1-7 achieved a drug release rate of 32.2%-38.5% at 2 hours and 86.8%-93.6% at 8 hours, exhibiting excellent sustained-release characteristics of stable release in the early stage and full release of active components in the later stage. The drug release rate of the samples using the modified chitosan and herbal compound system was further improved, with Example 7, which had a ternary chitosan formulation, showing the best drug release effect.

[0343] The drug release performance of each comparative example was significantly weaker than that of the example: the sample without a sustained-release functional layer did not have the ability to release the active component; the sample using simple drug spraying and half the effective antibacterial component showed a significant decrease in drug release rate at both time points; the sample with only changes to the absorption layer and bottom membrane structure showed a slight decrease in drug release performance, and the bottom membrane indirectly affected component diffusion by changing the system's medium exchange rate; after canceling the crosslinking process, the active component relied solely on physical adhesion and could not maintain a continuous and stable release, resulting in a significant decrease in drug release effect.

[0344] Experiments have confirmed that the gel-based sustained-release matrix system, cross-linking and immobilization process, and sufficient active ingredients are key to achieving pH-responsive controlled drug release. Compared to traditional drug spraying processes and simple, non-cross-linked adhesion structures, the present invention offers significant advantages in drug release stability and final release efficiency.

[0345] 4. Water absorption and retention effect test

[0346] The gynecological medical pads prepared in Examples 1-7 and the gynecological medical pads prepared in Comparative Examples 1-6 were tested for absorbency and water retention according to GB / T24218.1-2021, and the reabsorption performance was tested according to the method specified in GB / T 8939. The results are shown in Table 10 and... Figure 2 As shown.

[0347] Table 10: Test results of Examples 1-7 and Comparative Examples 1-6

[0348]

[0349] Examples 1-7 exhibited excellent overall absorption and water-locking performance, with an absorption range of 18.2-22.3g and a reabsorption rate as low as 0.09-0.14g. Among them, Example 2, a high-flow-rate formulation that enhances the bio-based SAP loading, showed the best absorption capacity; Example 7, which was formulated with seaweed fiber, demonstrated outstanding water-locking effect; the performance of the other basic formulations remained stable.

[0350] The comparative test results showed that after removing the composite functional layer, adopting a surface spraying process, replacing it with petroleum-based SAP and using adhesive bonding, using a dense bottom film, eliminating the skin-friendly layer crosslinking process, and reducing the amount of SAP added, all samples exhibited decreased absorption capacity and increased pressure-induced backflow. Adhesive easily clogs absorption channels, causing a decrease in the core's water absorption capacity; a dense bottom film alters the internal water vapor balance of the core, increasing the risk of liquid backflow; and uncrosslinked structures cannot effectively bind and absorb liquid. The performance degradation was most significant in the petroleum-based SAP bonding system and the sample with half the SAP content.

[0351] Tests have confirmed that the present invention, using a bio-based SAP system and a reasonable SAP loading, combined with a cross-linking molding process and a multi-layer composite functional layer structure, can simultaneously achieve high absorption capacity and low backflow effect. Its overall performance is significantly better than that of traditional petroleum-based absorbent materials, simple spraying processes, and non-cross-linked single-layer structure solutions.

[0352] 4. Breathability test

[0353] The gynecological medical pads prepared in Examples 1-7 and the gynecological medical pads prepared in Comparative Examples 1-6 were tested according to GB / T5453-2022, which specifies the test performance of air permeability of textiles. The results are shown in Table 11. Figure 2 As shown.

[0354] Table 11: Results of air permeability tests for Examples 1-7 and Comparative Examples 1-6

[0355]

[0356] Examples 1-7 show air permeability in the range of 342-395 mm / s, with excellent overall air permeability. Thickening the product increases airflow resistance, resulting in a slight decrease in air permeability. Samples made with bio-based fibers such as flax, bamboo, and seaweed fibers exhibit even better air permeability.

[0357] The comparative test results show that: the air permeability of the sample with only a reduction in the number of composite structure layers is improved; the effects of liquid spraying, skin-friendly layer process adjustment, and fiber raw material reduction on air permeability are small; when using glue bonding process, the glue will block the fiber gaps, and the air permeability will be significantly reduced; the air permeability of the sample with non-porous PE / EVA bottom film is greatly reduced, and the negative impact of non-porous petroleum-based plastic bottom film on air permeability is the most prominent.

[0358] Test results show that the bio-based fiber raw materials and multi-layer composite structure design selected in this invention can maintain excellent air permeability while ensuring core functions such as antibacterial, drug release, and water absorption and locking. The overall performance is significantly better than traditional solutions such as glue-bonded structures and non-porous plastic bottom films.

[0359] 5. Structural stability test

[0360] The gynecological medical pads prepared in Examples 1-7 and the gynecological medical pads prepared in Comparative Examples 1-6 were subjected to damp heat aging treatment at a temperature of 40°C and a relative humidity of 80% for 72 hours. The retention rate of mechanical strength of the samples was tested, and the results are shown in Table 12.

[0361] Table 12: Structural stability test results of Examples 1-7 and Comparative Examples 1-6

[0362]

[0363] The gynecological medical pads prepared in Examples 1-7 and the gynecological medical pads prepared in Comparative Examples 1-6 were subjected to 72 hours of humid heat accelerated aging treatment in an environment of 40°C and 80% relative humidity. The stability of the composite structure of the product was evaluated by testing the mechanical strength of the samples before and after aging and by the strength retention rate. The test results are shown in Table 12.

[0364] After aging for 72 hours under humid heat conditions of 40℃ and 80% relative humidity, the mechanical strength retention rate of Examples 1 to 7 reached 93.6% to 95.7%, demonstrating excellent resistance to humid heat aging and ability to maintain structural integrity. Among them, the PLA / PHA and PLA / PHBV bio-based bonding fiber system samples showed the best structural stability, and the thickened structure and multi-fiber composite scheme only brought about minor performance fluctuations.

[0365] The strength retention rate of each comparative example after aging was lower than that of all examples: the samples bonded with water-based adhesive, without chemical cross-linking, and with active components only sprayed on were prone to interface peeling under humid and hot conditions, and the mechanical strength decay was particularly significant; conventional three-layer structures, changing the bottom film material, and reducing the amount of functional components added also caused varying degrees of decrease in structural stability.

[0366] Experiments have shown that the present invention uses citric acid chemical crosslinking combined with hot melt composite process, and is compounded with bio-based bonding fibers, which can significantly improve the interfacial bonding ability of multilayer materials under humid and hot conditions. It is not easy to delaminate and break under long-term storage and humid use conditions, and its structural stability is significantly better than traditional molding processes such as water-based adhesive bonding and simple physical adhesion of components.

[0367] 6. Biodegradability test

[0368] The gynecological medical pads prepared in Examples 1-7 and the gynecological medical pads prepared in Comparative Examples 1-6 were subjected to biodegradability tests in accordance with GB / T19277.1-2011 Determination of final aerobic biodegradability of plastics under controlled composting conditions - Part 1: Method for measuring released carbon dioxide; the results are shown in Table 13.

[0369] Table 13: Biodegradation test results of Examples 1-7 and Comparative Examples 1-6

[0370]

[0371] Controlled composting degradation test results showed that the biodegradability rates of Examples 1-7 ranged from 92.6% to 94.2%, exhibiting excellent degradation performance and meeting the requirements for compostable biodegradable materials. Among them, Example 7, with its seaweed fiber compounded with ternary chitosan system, showed the best degradation effect. Increasing product thickness, adjusting the type of bio-fiber, and making minor adjustments to conventional processes had minimal impact on the overall degradation capacity.

[0372] The comparative test results showed that: for samples where only the antibacterial functional layer was removed, the skin-friendly layer process was adjusted, and the amount of functional components added was reduced, the main substrate remained a bio-based material, and the degradation rate was basically the same as that of the examples; after introducing chemical antibacterial agents, incorporating petroleum-based PP-SAP, and using PE / EVA petroleum-based membranes, the biodegradability rate of the samples decreased significantly. Chemical antibacterial agents inhibit the activity of microorganisms in the composting environment, hindering material degradation; petroleum-based polymers are difficult to be metabolized and decomposed by microorganisms, among which the negative impact of the PE / EVA base film on degradation performance is the most prominent.

[0373] Test results confirm that the invention uses all-bio-based raw materials combined with a natural antibacterial system, enabling the product to achieve efficient biodegradation. Compared with traditional panty liners that incorporate petroleum-based polymers and use chemical antibacterial agents, it has significant advantages in terms of green environmental protection.

[0374] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A bio-based biodegradable antibacterial gynecological medical pad, characterized in that: The product is formed by layering a skin-friendly layer, a pH-responsive micro-soluble drug-carrying functional layer, an absorbent layer, and a leak-proof bottom layer from top to bottom, followed by ultrasonic adhesive-free welding and post-processing. The skin-friendly layer uses bio-based fibers as the matrix, loads water-soluble chitosan antibacterial components, and is cross-linked with citric acid. The pH-responsive microsoluble drug-carrying functional layer includes supporting fibers, a polysaccharide matrix, a gel matrix, antibacterial components, and a crosslinking agent. The antibacterial components include chitosan-based antibacterial agents and plant-based soothing antibacterial components. The polysaccharide matrix and the gel matrix are combined to form a controllable swelling and release system under weakly acidic conditions. The absorbent layer is made of plant fibers, pulp and bio-based superabsorbent resin through web formation, thermal bonding and embossing. The leak-proof bottom layer is a bio-based biodegradable resin film, which is biaxially stretched to form a microporous structure that is breathable but impermeable to liquid.

2. The bio-based biodegradable antibacterial gynecological sanitary pad according to claim 1, characterized in that: The bio-based fibers in the skin-friendly layer are composed of main fibers, modified fibers, and bonding fibers; based on the total fiber mass: main fibers 55-65 wt%, modified fibers 20-25 wt%, and bonding fibers 15-20 wt%. The main fiber is selected from one or more of lyocell fiber, bamboo fiber, degreased long-staple cotton fiber, flax fiber, and seaweed fiber; The modified fiber is selected from one or more of alginate-modified viscose fiber, chitosan-modified viscose fiber, chitosan lyocell fiber, and aloe vera-modified viscose fiber. The bonding fiber is selected from one or more of PLA staple fiber, PLA / PBAT staple fiber, PLA / PHBV staple fiber, and PHA staple fiber.

3. The bio-based biodegradable antibacterial gynecological medical pad according to claim 1, characterized in that: The mass ratio of bio-based fibers to water-soluble chitosan antibacterial components in the skin-friendly layer is 100:0.4-0.8; the water-soluble chitosan antibacterial components are selected from one or more of carboxymethyl chitosan, hydroxypropyl chitosan, and quaternized chitosan.

4. The bio-based biodegradable antibacterial gynecological medical pad according to claim 1, characterized in that: The amount of chitosan-based antibacterial component added to the skin-friendly crosslinking finishing solution is 1.0-2.0 wt%, and the mass ratio of citric acid to chitosan-based antibacterial component is 1.0-2.5:1; the amount of sodium hypophosphite catalyst added is 10-20 wt% of the mass of citric acid; and the amount of fatty alcohol polyoxyethylene ether JFC-C penetrant added is 1-2 g / L based on the volume of deionized water.

5. The bio-based biodegradable antibacterial gynecological sanitary pad according to claim 1, characterized in that: In the pH-responsive microsoluble drug-carrying functional layer, based on the total mass of the supporting fibers, polysaccharide matrix, and gel matrix: supporting fibers 10-15 wt%, polysaccharide matrix 45-50 wt%, and gel matrix 40-45 wt%; the mass ratio of polysaccharide matrix to gel matrix is ​​1:0.8-1; the crosslinking agent is calcium lactate, added externally, at an amount of 2-5 wt% of the total mass of the supporting fibers, polysaccharide matrix, and gel matrix. The supporting fiber is selected from one or more of PLA microfiber, PHA microfiber, bamboo pulp microfiber, and PCL microfiber; the polysaccharide matrix is ​​selected from one or more of quaternized chitosan, quaternized carboxymethyl chitosan, and quaternized hydroxypropyl chitosan; and the gel matrix is ​​selected from one or more of sodium alginate, konjac glucomannan, and pectin.

6. A bio-based biodegradable antibacterial gynecological sanitary pad according to any one of claims 1 or 5, characterized in that: Within the pH-responsive, microsoluble drug-loaded functional layer, the mass ratio of chitosan-based antibacterial agent to plant-based soothing and antibacterial components is 3.0–9.0:1; the total amount of antibacterial components added is 8–15 wt% of the total mass of the supporting fibers, polysaccharide matrix, and gel matrix. The chitosan-based antibacterial agent is selected from one or more of quaternized carboxymethyl chitosan, quaternized chitosan, and quaternized hydroxypropyl chitosan; The plant-based soothing and antibacterial components are selected from one or more of Artemisia argyi extract, Sophora flavescens extract, dipotassium glycyrrhizate, and rosemary extract.

7. The bio-based biodegradable antibacterial gynecological sanitary pad according to claim 1, characterized in that: The mass percentages of each component in the absorbent layer are as follows: bio-based superabsorbent resin 40–47 wt%, plant fiber 30–32 wt%, composite pulp 20–23 wt%, and bonding fiber 3–5 wt%. The bio-based superabsorbent resin is a blend of alginate-based superabsorbent resin and cellulose-based superabsorbent resin, with a mass ratio of 3:7 to 7:3; the plant fiber is selected from one or two of degreased long-staple cotton and bamboo fiber; the composite pulp is selected from one or two of softwood pulp and cotton pulp; the bonding fiber is selected from PLA fiber and PLA / PBAT blended fiber.

8. The bio-based biodegradable antibacterial gynecological sanitary pad according to claim 1, characterized in that: The bio-based biodegradable resin of the leak-proof bottom layer is selected from one or more of PLA, PHA, PBS, PCL, and PBAT; the leak-proof bottom layer formulation includes bio-based biodegradable resin and external toughening agent 0.8-1.5 wt%, slip agent 0.3-1.0 wt%, chain extender 0.5-1.2 wt%, and pore-forming agent 10-15 wt%. The added toughening agent is an epoxy vegetable oil toughening agent, the slip agent is erucamide, the chain extender is ADR-4370S, and the pore-forming agent is selected from nano calcium carbonate, talc powder, and nano silica. The thin film preparation process involves biaxial stretching to create pores: longitudinal stretching ratio of 2.5 to 4.0 times, transverse stretching ratio of 2.0 to 3.5 times, and stretching temperature of 70 to 90℃.

9. The bio-based biodegradable antibacterial gynecological sanitary pad according to claim 1, characterized in that, Ultrasonic adhesive-free welding composite molding and post-processing parameters: ultrasonic frequency 20-40 kHz, power 800-1500 W; finished products are sterilized by 8-25 kGy electron beam irradiation.

10. A method for preparing a bio-based biodegradable antibacterial gynecological sanitary pad according to any one of claims 1 to 9, characterized in that, Includes the following steps: (1) Preparation of skin-friendly layer: open and mix bio-based fibers, comb them into a network, and reinforce them with three-stage incremental water pressure and hydroentangling; prepare a finishing solution containing chitosan and citric acid for impregnation and finishing, and dry and cross-link to form a shape; (2) Preparation of pH-responsive microsoluble drug-loaded functional layer: ultrafine supporting fibers are dispersed, a coating solution containing polysaccharide matrix, gel matrix, antibacterial component and crosslinking agent is prepared, coated on the inner side of the skin-friendly layer, and dried at low temperature to crosslink and form pH-responsive microsoluble drug-loaded gel layer. (3) Preparation of absorbent layer: plant fiber and composite pulp are loosened and dispersed, airflow is used to form a network and bio-based superabsorbent resin is simultaneously sprinkled, negative pressure adsorption, hot air bonding, and micro-embossing are performed. (4) Preparation of leak-proof bottom layer: The matrix resin is blended and granulated with various additives, blown into film, biaxially stretched to form holes, heat-set and wound up; (5) Four-layer ultrasonic adhesive-free welding composite and post-processing: ultrasonic welding composite, edge heat sealing, slicing, individual packaging, and electron beam irradiation sterilization to obtain the finished pad.

Citation Information

Patent Citations

  • Highly-antibacterial novel slightly-soluble healthcare sanitary pad capable of adsorbing heavy metal particles

    CN105616075A

  • Efficient bacteriostatic blast bead essential oil sanitary pad and preparation method thereof

    CN118383945A